Low dielectric loss glasses for electronic devices

A glass composition with a specific oxide ratio and alkaline earth oxide content addresses the manufacturing challenges of high-frequency glasses by achieving low dielectric constant and loss tangent while maintaining suitable viscosity for molding, making it suitable for electronic device applications.

JP2025039835APending Publication Date: 2025-03-21CORNING INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2025005288
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-01-21
Filing Date
2025-01-15
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing glasses with low dielectric constant and low loss tangent at 10 GHz frequencies are challenging to manufacture using common molding methods due to high liquidus viscosity, which limits their practical application in electronic devices.

Method used

A glass composition comprising 60% to 80% SiO2, 0% to 13% Al2O3, 15% to 28% B2O3, and 0% to 1% clarifier, with additional alkaline earth oxides such as MgO, CaO, BaO, and SrO, achieving a relative permittivity of less than 10 and a loss tangent of less than 0.01 at 10 GHz, while maintaining a suitable liquidus viscosity for molding processes.

Benefits of technology

The glass composition effectively balances dielectric properties and formability, enabling the production of glasses suitable for high-frequency electronic device applications without the limitations of high liquidus viscosity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039835000001_ABST
    Figure 2025039835000001_ABST
Patent Text Reader

Abstract

To provide glass articles having a low loss tangent.SOLUTION: There is provided a glass article that includes a glass including SiO2 from about 60% to about 80%, Al2O3 from 0% to about 13%, B2O3 from about 15% to about 28%, from 0% to about 1% of at least one clarifying agent, and MgO and at least one additional alkaline earth oxide (RO), wherein the at least one additional RO is selected from CaO, BaO, and SrO, and wherein a total amount of MgO plus the at least one additional RO (ROTotal) is from about 3% to about 15% (by mole of oxide). The glass includes a dielectric constant of about 10 or less and / or a loss tangent of about 0.01 or less, both as measured with signals at 10 GHz.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims priority under 35 U.S.C. § 119 to U.S. Patent Application No. 62,794,226, filed January 18, 2019, and U.S. Patent Application No. 62 / 794,869, filed January 21, 2019, both of which are incorporated by reference in their entireties. This application is a divisional application of Japanese Patent Application No. 2021-541291, filed January 16, 2020. [Technical field]

[0002] The present disclosure relates generally to glasses having low dielectric constants and low loss tangents as measured with a 10 GHz signal, and more particularly to such glasses suitable for electronic device applications. [Background technology]

[0003] Digital technology continues to expand, especially with regard to data connectivity and processing speeds. For example, processing speeds on the order of 1 Gbit / s are expanding to speeds on the order of tens of Gbit / s. To achieve these data rates, the corresponding electronic device technology may result in signal transmission and reception frequencies on the order of 1 GHz expanding to 10 GHz and possibly even up to about 100 GHz.

[0004] As these signal frequencies increase to accommodate increasing data processing speeds, technical specifications and requirements related to absorption losses associated with insulating materials employed in these devices become more critical. There are materials available that have low loss tangents at frequencies above 10 GHz, but the processing characteristics of these materials may limit their manufacturability using certain molding processes. For example, materials such as radome pyroceramics, high purity fused silica, sapphire, alumina, and silica may have low loss tangents at frequencies above 10 GHz. However, these materials may have high viscosities at molding temperatures that may limit their fabrication using molding processes such as slot draw and overflow downdraw. There are also alkali-free glass and glass-ceramic materials with low loss tangents at frequencies above 10 GHz, such as the B2O3-P2O5-SiO2 (BPS) and MgO-Al2O3-SiO2 (MAS) ternary systems. Summary of the Invention [Problem to be solved by the invention]

[0005] However, these systems typically have liquidus viscosities that are too low for common molding processes.A need exists for glasses that overcome some or all of the above problems. [Means for solving the problem]

[0006] According to one embodiment of the present disclosure, an article includes a glass comprising (by component content) about 60% to about 80% (i.e., molar %) SiO2, 0% to about 13% Al2O3, about 15% to about 28% B2O3, and 0% to about 1% of at least one fining agent. The glass also comprises (by oxide molar percentage) 0% to about 8% total of one or more alkaline earth oxides (RO), where RO is selected from CaO, MgO, BaO, and SrO. The glass can be characterized by a ratio of B2O3:(Al2O3+SiO2) between about 0.13 and about 0.35, and can have a dielectric constant of about 10 or less and a loss tangent of about 0.01 or less, both measured with a 10 GHz signal.

[0007] According to one embodiment of the present disclosure, an article includes a glass including (by component content) about 60% to about 80% SiO2, 0% to about 13% Al2O3, about 15% to about 28% B2O3, and 0% to about 1% of at least one fining agent. The glass can also include (by oxide mole percent) 0% to about 8% total of one or more alkaline earth oxides (RO), where RO is selected from CaO, MgO, BaO, and SrO. The glass can be characterized by a ratio of RO:(Al2O3+(0.5*B2O3)) that is 0 to about 0.9, and can further have a liquidus viscosity of about 40 kpoise to 5000 kpoise.

[0008] According to one embodiment of the present disclosure, an article includes a glass comprising (by component content) about 60% to about 80% SiO2, 0% to about 13% Al2O3, about 15% to about 28% B2O3, and 0% to about 1% of at least one fining agent. The glass also comprises (by oxide mole percent) 0% to about 8% total of one or more alkaline earth oxides (RO), where RO is selected from CaO, MgO, BaO, and SrO. The glass can be characterized by a ratio of B2O3:(Al2O3+SiO2) between about 0.13 and about 0.35, and can have a dielectric constant of about 10 or less and a loss tangent of about 0.01 or less, both measured with a 10 GHz signal. The glass can be further characterized by a liquidus viscosity of about 40 kpoise to about 5000 kpoise.

[0009] According to one embodiment of the present disclosure, an article includes a glass comprising (by component content) about 60% to about 80% SiO2, 0% to about 13% Al2O3, about 15% to about 28% B2O3, 0% to about 1% of at least one fining agent, and MgO and at least one additional alkaline earth oxide (RO), where the at least one additional RO is selected from CaO, BaO, and SrO, and the total amount of MgO and the at least one additional RO combined (RO Total ) is about 3% to about 15% (in terms of oxide mole percent). All of the above glasses have a dielectric constant of about 10 or less and / or a loss tangent of about 0.01 or less when measured with a 10 GHz signal.

[0010] According to one aspect of the present disclosure, an article for a substrate of an electronic device includes a glass consisting essentially of (by component content) about 60% to about 80% SiO, 0% to about 13% AlO, about 15% to about 28% BO, 0% to about 1% of at least one fining agent, and MgO and at least one additional alkaline earth oxide (RO), where the at least one additional RO is selected from CaO, BaO, and SrO, and the total amount of MgO and the at least one additional RO combined (RO Total ) is about 3% to about 15% (in terms of oxide mole percent). All of the above glasses have a dielectric constant of about 10 or less and / or a loss tangent of about 0.01 or less when measured with a 10 GHz signal.

[0011] According to one aspect of the disclosure, an article includes a glass including (by component content) SiO2, Al2O3, and B2O3, and at least one of Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, SnO2, ZnO, La2O3, F, and Fe2O3, where a first sum (X2O3) of SiO2, Al2O3, and B2O3 is 0.01 to 0.01% by weight. sum ), the second sum of Li2O, Na2O, K2O, MgO, CaO, SrO, and BaO (Y sum ), and the sum of SnO2, ZnO, La2O3, F, and Fe2O3 third (Z sum )(Xsum , Y sum , and Z sum is the mole percent of oxide) at the boundary points: TIFF2025039835000002.tif46160

[0012] X as further defined by sum , Y sum , and Z sum is in the convex hull of The glass further comprises (in mole percent of oxides) Formula 1 and Formula 2: -42.8440902+0.463763055*[SiO2]+0.520077325*[Al2O3]+0.468168738 *[B2O3]+0.47253232*[Li2O]+2.11958583*[K2O]+0.499421381*[MgO]+0. 558094225*[CaO]+0.805792958*[SrO]+0.637349469*[BaO]-0.17232118* [SnO2]+0.525853343*[ZnO]+0.261394654*[La2O3]+0.469279089*[F]≦10 formula 1 and 0.756212572817506+[K2O]+0.209148876828416*[La2O3]+0.0884393206156657*[BaO]+0.0384462744417 211*[CaO]+(5.95212630529679-[F]) / [B2O3]+(254.196472343803-2.1615185467817*[B2O3]) / [SiO2]≦10 formula 2 is defined by at least one of The glass has a dielectric constant of about 10 or less when measured with a 10 GHz signal.

[0013] According to another aspect of the disclosure, an article includes a glass including (by component content) SiO2, Al2O3, and B2O3, and at least one of Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, SnO2, ZnO, La2O3, F, and Fe2O3, where a first sum (X2O3) of SiO2, Al2O3, and B2O3 is 0.01 to 0.01% by weight. sum ), the second sum of Li2O, Na2O, K2O, MgO, CaO, SrO, and BaO (Y sum ), and the third sum of SnO2, ZnO, La2O3, F, and Fe2O3 (Z sum )(X sum , Y sum , and Z sum is the mole percent of oxide) at the boundary points: TIFF2025039835000003.tif97157

[0014] X as further defined by sum , Y sum , and Z sum is in the convex hull of The glass further comprises (in mole percent of oxides) Formula 1 and Formula 2: -42.8440902+0.463763055*[SiO2]+0.520077325*[Al2O3]+0.468168738 *[B2O3]+0.47253232*[Li2O]+2.11958583*[K2O]+0.499421381*[MgO]+0. 558094225*[CaO]+0.805792958*[SrO]+0.637349469*[BaO]-0.17232118* [SnO2]+0.525853343*[ZnO]+0.261394654*[La2O3]+0.469279089*[F]≦10 formula 1 and 0.756212572817506+[K2O]+0.209148876828416*[La2O3]+0.0884393206156657*[BaO]+0.0384462744417 211*[CaO]+(5.95212630529679-[F]) / [B2O3]+(254.196472343803-2.1615185467817*[B2O3]) / [SiO2]≦10 formula 2 is defined by at least one of The glass has a dielectric constant of about 10 or less when measured with a 10 GHz signal.

[0015] Additional features and advantages are set forth in the following detailed description, and in part will become readily apparent to those skilled in the art from the detailed description or by practicing the embodiments described herein, including the following detailed description, the claims, and the accompanying drawings.

[0016] It should be understood that both the foregoing Summary and the following Detailed Description are merely examples, and are intended to provide an overview or framework for understanding the nature and character of the claims. The accompanying drawings are included to provide a further understanding, and are incorporated in and constitute a part of this specification. The drawings illustrate one or more embodiments, and together with the description, serve to explain the principles and operation of these various embodiments. [Brief description of the drawings]

[0017] [Figure 1] 1 is a chart showing the dielectric constant and loss tangent measured at a signal frequency of 10 GHz for exemplary glasses according to the present disclosure and comparative materials. [Diagram 2] FIG. 1 is a plot of a two-dimensional convex hull defined by the boundary points of the sum of SiO, AlO, and BO (Xsum) and the sum of LiO, NaO, KO, MgO, CaO, SrO, and BaO (Ysum) for a glass according to an embodiment of the present disclosure. [Diagram 3] FIG. 1 is a plot of a two-dimensional convex hull defined by the boundary points of the sum of SiO, AlO, and BO (Xsum) and the sum of LiO, NaO, KO, MgO, CaO, SrO, and BaO (Ysum) of a glass, according to an embodiment of the present disclosure. [Figure 4] 1 is a plot of predicted dielectric constant (Dk) as a function of measured dielectric constant (Dk) for a series of glass compositions according to certain embodiments of the present disclosure. [Diagram 5] 1 is a plot of predicted dielectric constant (Dk) as a function of measured dielectric constant (Dk) for a series of glass compositions according to certain embodiments of the present disclosure. [Figure 6] 1 is a plot of predicted loss tangent as a function of measured loss tangent for a series of glass compositions according to certain aspects of the present disclosure. [Figure 7] 1 is a plot of predicted loss tangent as a function of measured loss tangent for a series of glass compositions according to certain aspects of the present disclosure. [Figure 8A] 1 is a plot of measured dielectric constant (Dk) for a series of glass compositions as a function of alkaline earth oxide (RO) concentration, according to certain embodiments of the present disclosure. [Figure 8B] 1 is a plot of measured loss tangent for a series of glass compositions as a function of alkaline earth oxide (RO) concentration, according to an embodiment of the present disclosure; [Figure 9A] 1 is a plot of measured dielectric constant (Dk) for a series of glass compositions as a function of the ratio of the amount of MgO, CaO, or BaO to the total amount of alkaline earth oxides (ROTotal), according to an embodiment of the present disclosure. [Figure 9B] 1 is a plot of measured loss tangent for a series of glass compositions as a function of the ratio of the amount of MgO, CaO, or BaO to the total amount of alkaline earth oxides (ROTotal), according to an embodiment of the present disclosure; [Figure 10A] 1 is a plot of measured dielectric constant (Dk) for a series of glass compositions having a single RO species or mixed RO species as a function of glass density, according to certain embodiments of the present disclosure. [Figure 10B]1 is a plot of measured loss tangent for a series of glass compositions having a single RO species or a mixture of RO species as a function of glass density, according to an embodiment of the present disclosure; [Figure 11] Plot of predicted dielectric constant (Dk) as a function of measured dielectric constant (Dk) for a series of glass compositions having a single RO species or a mixture of RO species. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] In the following "Description of the Preferred Embodiments," for purposes of explanation and not limitation, exemplary embodiments disclosing specific details are described to provide a thorough understanding of the various principles of the present disclosure. However, it will be apparent to one of ordinary skill in the art having the benefit of this disclosure that the present disclosure can be practiced in other embodiments that depart from the specific details disclosed herein. Moreover, descriptions of well-known devices, methods, and materials may be omitted so as not to obscure the description of the various principles of the present disclosure. Finally, wherever applicable, like reference numerals refer to like elements.

[0019] Ranges may be expressed herein as from "about" one particular value, and / or to "about" another particular value. When such a range is expressed, another embodiment includes from the one particular value and / or to the other particular value. Similarly, when values ​​are expressed as approximations, by use of the antecedent "about," it will be understood that the particular value forms another embodiment. It will be further understood that the endpoints of each of the ranges are significant both in relation to the other endpoint, and independently of the other endpoint.

[0020] Unless otherwise specified, all compositions are expressed in as-batched (i.e., component content) mole percent (mol%). As will be understood by those skilled in the art, various melting components (e.g., fluorine, alkali metals, boron, etc.) may undergo different levels of volatilization during melting of these components (e.g., depending on vapor pressure, melting time, and / or melting temperature). Thus, the term "about" with respect to such components is intended to encompass values ​​within about 1 mol% when measured on the final article compared to the as-batched compositions provided herein. With the above in mind, substantial compositional equivalence is expected between the final article and the as-batched compositions.

[0021] Unless otherwise stated, it is in no way intended that any method described herein be construed as requiring that its steps be performed in a particular order. Thus, if a method claim does not actually recite the order in which its steps are to be followed, or if it is not specifically stated in the claim or description that the steps are to be limited to a particular order, no one order is intended to be presumed in any way. This applies to any implicit basis for interpretation, including: questions of logic regarding the arrangement or operational flow of steps; apparent meaning derived from grammatical construction or punctuation; or the number or type of embodiments described herein.

[0022] As used herein, the term "convex hull" refers to the smallest convex set that encloses a set of N points in Euclidean space. In the present disclosure, the N points that define the convex hull are based on the sum of the concentrations of a given set of oxides that may be present in the glass precursor composition (i.e., the as-batched glass composition). The N points that define the convex hull are expressed as coordinates in a three-dimensional Cartesian coordinate system having an origin 0 and X, Y, and Z coordinate axes. Each coordinate corresponds to the sum of the concentrations of a given subset of the given set of oxides that may be present in the glass precursor composition. The X, Y, and Z coordinates respectively represent the sum of the X, Y, and Z concentrations of the given subset of oxides. sum, Y sum , and Z sum As used herein, a "boundary point" refers to the N points that define the convex hull, expressed as coordinates in a three-dimensional Cartesian coordinate system having an origin 0 and X, Y, and Z coordinate axes.

[0023] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly indicates otherwise. Thus, for example, reference to "a component" includes aspects having two or more such components, unless the context clearly indicates otherwise.

[0024] As used herein, the term "CTE" refers to the coefficient of thermal expansion of the glass materials, elements, and the like in the present disclosure averaged over a temperature range of about 20° C. to about 300° C., unless otherwise specified.

[0025] The terms "thin glass" or "relatively thin glass" are used interchangeably with respect to laminated glass structures in this disclosure and are intended to mean a laminated structure having a total thickness of about 3 mm or less.

[0026] The term "thickness-weighted average dielectric constant (D k )(thickness weighted average dielectric constant(D k "D )" refers to the dielectric constant of a glass structure, design, or article of the present disclosure. In particular, the thickness-weighted average dielectric constant (D k ) is calculated by multiplying the thickness of the or each layer of a multi-layer laminate structure by the estimated or measured dielectric constant, summing the products for each of the layers, and dividing this sum by the total thickness of the glass structure. As used herein, the term "dielectric constant" refers to the thickness-weighted average dielectric constant D, unless otherwise specified. k, and are used interchangeably.

[0027] The terms "loss tangent", "dielectric loss tangent", and "dielectric loss" are used interchangeably in this disclosure to refer to the inherent dissipation of electromagnetic energy (e.g., heat) provided by a particular glass, layer, or laminate structure associated with an embodiment of this disclosure. The lower the dielectric loss (e.g., the portion of energy lost as heat), the more effective the dielectric material. The loss tangent can be parameterized in terms of either the loss angle δ or the corresponding loss tangent tan δ. Permittivity is the ability of a material, such as the glasses of this disclosure, to store electrical energy in the presence of an external electric field. Additionally, the terms "permittivity" and "average relative permittivity (D k )(average dielectric constant(D k The terms "mean dielectric constant (D ))" and "average dielectric constant (D )" are used interchangeably in this disclosure. Dielectric constant is a quantity that measures the ability of a material to store electrical energy in an electric field. Dielectric constant is a complex quantity because it describes the phase and magnitude of the polarization associated with an oscillating field. The term "average dielectric constant (D k ) and Relative Permittivity (ε r )(relative permittivity(ε r )) are used interchangeably in this disclosure and are defined as the ratio between the real part of the complex permittivity (absolute permittivity) and the permittivity of free space (vacuum permittivity). ε rMaterials with a dielectric constant >1 are considered to be dielectric materials and poor conductors of electricity, and materials with a relatively low dielectric constant can withstand stronger electrostatic fields without dielectric breakdown, which occurs in materials that conduct electric current (which leads to material damage in most solid materials). "Loss tangent" is expressed as the ratio between the imaginary and real parts of the complex dielectric constant. In general, the average dielectric constant and loss tangent of a material depend on the frequency of the external field. Thus, dielectric properties measured in the kHz range may not represent the dielectric properties at microwave frequencies. Furthermore, unless otherwise specified, the "loss tangent" and "average dielectric constant (D k The "measurement method" attribute can be measured at frequencies above 1 GHz by a split post dielectric resonator (SPDR) or open cavity resonator configuration according to techniques as would be understood by one of ordinary skill in the art of the present disclosure. The particular method selected can be selected based on the thickness of the sample and its lateral dimensions.

[0028] Embodiments of the present disclosure relate to articles comprising glasses having a dielectric constant of about 10 or less and / or a loss tangent of about 0.01 or less, and in some embodiments a loss tangent of about 0.008 or less, when measured at a signal frequency of about 10 GHz or more. The glasses of the present disclosure can be used in various electronic devices, such as antennas, semiconductor circuits, signal transmission structures, and printed circuit board (PCB) substrates. In one embodiment, the glass compositions of the present disclosure can be used to form various laminated glass structures, designs, and articles.

[0029] In some embodiments, the glasses of the present disclosure include SiO2, Al2O3, and B2O3, and at least one of Li2O, Na2O, KO, MgO, CaO, SrO, BaO, SnO2, ZnO, La2O3, F, and Fe2O3. According to one embodiment of the present disclosure, the amount of each oxide present in the glass is determined by the boundary point X sum , Y sum , and Z sum in the composition space corresponding to the convex hull defined by, where X sumis based on the first sum of SiO2, Al2O3, and B2O3, and Y sum is based on the second sum of Li2O, Na2O, K2O, MgO, CaO, SrO, and BaO, and Z sum is based on a third sum of SnO2, ZnO, La2O3, F, and Fe2O3. In one embodiment, the glass composition is sum , Y sum , and Z sum , and which has a dielectric constant of less than or equal to about 10 and / or a loss tangent of about 0.008 when measured at a frequency of about 10 GHz.

[0030] In some embodiments, the glasses of the present disclosure can include SiO2, B2O3, and optionally Al2O3. In some embodiments, the amounts of SiO2, B2O3, and Al2O3 can be present in the glasses according to a specified ratio of B2O3:(Al2O3+SiO2). For example, the glasses of the present disclosure can have a ratio of B2O3:(Al2O3+SiO2) that is about 0.13 to about 0.35. In some implementations, the glasses further include one or more alkaline earth oxides (RO), where RO is CaO, MgO, BaO, and / or SrO. Optionally, the glasses can include additional components, such as fining agents. In some implementations, the glasses include only trace amounts of alkali metal oxides, and thus are substantially free of alkali metals. In some implementations, no alkali metal oxides are intentionally added to the glasses. As used herein, "trace amount" or "substantially free" refers to an amount less than 0.2 mole percent.

[0031] In some embodiments, the glasses of the present disclosure can include SiO, B0, and optionally Al0, and can also include MgO and at least one additional alkaline earth oxide (RO) in a total amount of MgO and the at least one additional RO (RO Total) in an amount of about 3 mol% to about 15 mol%. The at least one additional RO can be selected from CaO, BaO, and SrO. The combination of MgO and the at least one additional RO according to embodiments of the present disclosure can facilitate the formation of a glass having a lower dielectric constant and / or loss tangent compared to some glasses containing only a single RO species.

[0032] Implementations of the glasses of the present disclosure may be suitable for electronic devices, electronic device substrates, and other similar applications, where these implementations allow relatively high frequency communication within the device without significant degradation in performance as it relates to other non-electrical device requirements. For example, these devices use relatively high frequency communication signals that must pass through various physical barriers that would otherwise attenuate or block these signals. Thus, the glasses of the present disclosure may be highly suitable for use as these barriers. Examples of these physical barriers are: electrically insulating substrates used in the fabrication of electronic circuits and signal transmission structures; as well as device covers and other related structures that can be used to house circuits and other electronic device components employed in electronic devices that operate at high signal frequencies.

[0033] In some implementations, the glasses of the present disclosure are suitable for use as substrates in PCBs. PCBs typically include an insulating layer laminated with a copper film. In some implementations, the glasses of the present disclosure are characterized by low loss tangent and mechanical properties suitable for use as an insulating layer in PCBs, optionally in combination with one or more polymer substrate layers. Optionally, the glasses of the present disclosure can be substantially free of alkali metals to reduce the possibility of ion migration during processing.

[0034] Some aspects of the present disclosure also relate to glasses that have properties that make them suitable for manufacturing, particularly for forming processes such as slot draw, overflow fusion draw, and laminate fusion molding. The fusion draw process is an industrial technique used for the large-scale production of thin glass sheets. Compared to other flat glass manufacturing techniques such as float or slot draw processes, the fusion draw process results in thin glass sheets with high flatness and surface quality. As a result, the fusion draw process is often the dominant manufacturing technique in the fabrication of thin glass substrates (e.g., for liquid crystal displays and for cover glass of various personal electronic devices).

[0035] The fusion draw process involves flowing molten glass over a trough known as an "isopipe," which is typically made of zircon or another refractory material. The molten glass flows over the top of the isopipe from both sides and meets at the bottom of the isopipe to form a single sheet, with only the inside of the final sheet being in direct contact with the isopipe. Because the exposed surfaces of the final glass sheet do not come into contact with isopipe material during the draw process, both outer surfaces of the glass can be of clean quality and not require subsequent finishing.

[0036] To facilitate the fusion draw process, the glass desirably has a sufficiently high liquidus viscosity (i.e., the viscosity of the molten glass at the liquidus temperature). A high liquidus viscosity can facilitate shaping of the glass by a downdraw process such as fusion forming. Furthermore, the fusion draw process operates over a range of viscosities. Glass is typically delivered to the trough of the isopipe at a viscosity corresponding to about 20,000-35,000 poise and leaves the base of the isopipe at a viscosity corresponding to about 100,000 poise or more. A temperature corresponding to a viscosity of 35,000 poise is often used as a guide for the temperature at which the glass will be delivered to the trough of the isopipe for fusion drawing. The glasses of the present disclosure have a temperature corresponding to 35,000 poise (referred to herein as the "35,000 poise temperature") that facilitates shaping by the downdraw process. Typically, a low 35,000 poise temperature is desired to minimize undesirable creep of the isopipe's refractory material over time.

[0037] The temperature corresponding to 200 poise is often used as a guideline for a suitable melting point of a glass. In some implementations, the glasses of the present disclosure are characterized by a relatively high 200 poise temperature, also referred to as the Poise Melting Point, to facilitate molding (also referred to herein as the "200 Poise Melting Point").

[0038] As discussed above, conventional fusion draw processes are accomplished using a single isopipe to produce a homogenous glass product. More complex fusion draw processes can be used to form laminated articles including the glasses of the present disclosure. In a laminate fusion draw process, two isopipes are employed to form a laminated sheet that includes a core composition surrounded on one or both sides by an outer cladding layer.

[0039] The glasses of the present disclosure can be formed into articles and structures having an average coefficient of thermal expansion (CTE) suitable for use in forming various electronic devices. According to one embodiment, the glasses of the present disclosure are characterized by CTE values ​​suitable for use as core and / or cladding layers in laminates (e.g., mechanically strengthened laminates) or as substrates in PCBs.

[0040] The glass of the present disclosure can include SiO2 in an amount of about 50% (mol%) to about 80 mol%, in terms of oxide mole %, in some embodiments, the amount of SiO2 is about 50 mol% to about 80 mol%, about 50 mol% to about 78 mol%, about 50 mol% to about 75 mol%, about 50 mol% to about 70 mol%, about 50 mol% to about 65 mol%, about 52 mol% to about 80 mol%, about 52 mol% to about 78 mol%, about 52 mol% to about 75 mol%, about 52 mol% to about 70 mol%, about 52 mol% to about 65 mol%, about 54 mol% to about 80 mol%, about 54 mol% to about 78 mol%, about 54 mol% to about 75 mol%, about 54 mol% to about 70 mol%, about 54 mol% to about 54 ... mol% to about 65 mol%, about 64 mol% to about 75 mol%, about 60 mol% to about 80 mol%, about 60 mol% to about 75 mol%, about 60 mol% to about 70 mol%, about 60 mol% to about 65 mol%, about 65 mol% to about 70 mol%, about 65 mol% to about 75 mol%, about 65 mol% to about 80 mol%, about 64 mol% to about 70 mol%, about 64 mol% to about 75 mol%, about 64 mol% to about 80 mol%, about 70 mol% to about 75 mol%, about 70 mol% to about 80 mol%, or about 75 mol% to about 80 mol%. In some embodiments, the amount of SiO2 can be about 50 mol%, about 52 mol%, about 54 mol%, about 60 mol%, about 64 mol%, about 65 mol%, about 68 mol%, about 69 mol%, about 70 mol%, about 71 mol%, about 72 mol%, about 73 mol%, about 74 mol%, about 75 mol%, about 80 mol%, or any amount of SiO2 between these values.

[0041] The glasses of the present disclosure can include B2O3 in an amount of about 7 mol% to about 28 mol%. In some embodiments, the amount of B2O3 can be about 7 mol% to about 28 mol%, about 7 mol% to about 26 mol%, about 7 mol% to about 25 mol%, about 7 mol% to about 20 mol%, about 9 mol% to about 28 mol%, about 9 mol% to about 26 mol%, about 9 mol% to about 25 mol%, about 9 mol% to about 20 mol%, about 15 mol% to about 28 mol%, about 16 mol% to about 26 mol%, about 15 mol% to about 28 mol%, about 15 mol% to about 25 mol%, about 15 mol% to about 20 mol%, about 15 mol% to about 18 mol%, about 20 mol% to about 28 mol%, about 20 mol% to about 26 mol%, about 20 mol% to about 24 mol%, or about 20 mol% to about 22 mol%. In some embodiments, the amount of B2O3 can be about 7 mol%, about 8 mol%, about 9 mol%, about 10 mol%, about 11 mol%, about 12 mol%, about 13 mol%, about 14 mol%, about 15 mol%, about 16 mol%, about 17 mol%, about 18 mol%, about 19 mol%, about 20 mol%, about 21 mol%, about 22 mol%, about 23 mol%, about 24 mol%, about 25 mol%, about 26 mol%, about 27 mol%, about 28 mol%, or any amount of B2O3 between these values.

[0042] The glasses of the present disclosure can include Al2O3 in amounts from 0 mol % to about 15 mol %. In some embodiments, the amount of Al2O3 is from about 0 mol% to about 15 mol%, from about 0 mol% to about 14 mol%, from about 0 mol% to about 13 mol%, from about 0 mol% to about 12 mol%, from about 0.05 mol% to about 15 mol%, from about 0.05 mol% to about 14 mol%, from about 0.05 mol% to about 13 mol%, from about 0.05 mol% to about 12 mol%, from about 0.09 mol% to about 15 mol%, from about 0.09 mol% to about 14 mol%, from about 0.09 mol% to about 13 mol%, from about 0.09 mol% to about 12 mol%, from about 0.1 mol% to about 15 mol%, from about 0.1 mol% to about 14 mol%, from about 0.1 mol% to about 13 mol%, from about 0.1 mol% to about 12 mol%, from about 1 mol% to about 1 5 mol%, about 1 mol% to about 12 mol%, about 0.1 mol% to about 13 mol%, about 1 mol% to about 13 mol%, about 1 mol% to about 10 mol%, about 1 mol% to about 7 mol%, about 1 mol% to about 5 mol%, about 1 mol% to about 3 mol%, about 3 mol% to about 15 mol%, about 3 mol% to about 13 mol%, about 3 mol% to about 10 mol%, about 3 mol% to about 7 mol%, about 3 mol% to about 5 mol%, about 5 mol% to about 15 mol%, about 5 mol% to about 13 mol%, about 5 mol% to about 10 mol%, about 5 mol% to about 7 mol%, about 7 mol% to about 15 mol%, about 7 mol% to about 13 mol%, about 7 mol% to about 10 mol%, or about 10 mol% to about 13 mol%. In some embodiments, the amount of Al2O3 is about 0 mol%, about 0.05 mol%, about 0.09 mol%, about 0.1 mol%, about 1 mol%, about 2 mol%, about 3 mol%, about 4 mol%, about 5 mol%, about 6 mol%, about 7 mol%, about 8 mol%, about 10 mol%, about 11 mol%, about 12 mol%, about 13 mol%, about 14 mol%, about 15 mol%, or any amount of Al2O3 between these values.

[0043] Increasing the amount of SiO2 can reduce the dielectric constant and loss tangent of the glass at frequencies above 10 GHz, but increasing the amount of SiO2 reduces the formability of the glass, especially the formability by the down-draw process. For example, as the amount of SiO2 increases, the liquidus temperature of the glass can increase. Pure SiO2 has a low CTE and is not compatible with the down-draw process due to its high melting point. By adding B2O3, the viscosity of the glass can be reduced and the liquidus viscosity can be reduced to facilitate the forming of the glass, especially by the down-draw process. B2O3 can have the effect of reducing the liquidus temperature more quickly compared to the viscosity, thus improving the liquidus viscosity for forming by the down-draw process. Al2O3 can reduce the liquidus temperature and therefore increase the liquidus viscosity. Thus, the amount of SiO2, B2O3, and optionally Al2O3 can be selected according to the present disclosure to balance the desired dielectric properties and formability of the glass. In some embodiments of the present disclosure, the amounts of SiO2, B2O3, and Al2O3 in the glass may be selected to provide a ratio of B2O3:(Al2O3+SiO2) of about 0.13 to about 0.35. In some embodiments, the ratio of B2O3:(Al2O3+SiO2) is about 0.13 to about 0.35, about 0.13 to about 0.34, about 0.13 to about 0.3, about 0.13 to about 0.28, about 0.13 to about 0.26, about 0.13 to about 0.24, about 0.13 to about 0.22, about 0.13 to about 0.2, about 0.22 to about 0.3. 0.5, about 0.22 to about 0.24, about 0.29 to about 0.34, about 0.28 to about 0.35, about 0.22 to about 0.3, about 0.22 to about 0.28, about 0.22 to about 0.26, about 0.24 to about 0.35, about 0.24 to about 0.3, about 0.24 to about 0.28, about 0.26 to about 0.35, or about 0.26 to about 0.3. In some embodiments, the ratio of B2O3:(Al2O3 + SiO2) is about 0.13, about 0.14, about 0.15, about 0.16, about 0.17, about 0.18, about 0.19, about 0.2, about 0.21, about 0.22, about 0.23, about 0.24, about 0.29, about 0.30, about 0.31, about 0.32, about 0.33, or about 0.34.

[0044] In some implementations, the amount of SiO2 and B2O3 is selected such that the sum of SiO2 and B2O3 is about 86 mol% to about 97 mol%. In some embodiments, the sum of SiO2 and B2O3 can be about 86 mol% to about 97 mol%, about 86 mol% to about 94 mol%, about 86 mol% to about 90 mol%, about 86 mol% to about 88 mol%, about 90 mol% to about 97 mol%, about 90 mol% to about 94 mol%, about 93 mol% to about 97 mol%, or about 94 mol% to about 97 mol%. In some embodiments, the sum of SiO2 and B2O3 can be about 86 mol%, about 87 mol%, or about 88 mol%.

[0045] In some implementations, the amounts of SiO2, B2O3, and Al2O3 in the glass are selected such that the sum of SiO2, B2O3, and Al2O3 is between about 60 mol% and about 99.9 mol%. In some embodiments, the sum of SiO2, B2O3, and Al2O3 is between about 60 mol% and about 99.9 mol%, between about 60 mol% and about 95 mol%, between about 60 mol% and about 90 mol%, between about 60 mol% and about 85 mol%, between about 60 mol% and about 80 mol%, between about 60 mol% and about 75 mol%, between about 60 mol% and about 70 mol%, between about 65 mol% and about 99.9 mol%, between about 65 mol% and about 95 mol%, between about 65 mol% and about 90 mol%, between about 65 mol% and about 85 mol%, between about 65 mol% and about 80 mol%, between about 65 mol% and about 75 mol%, between about 65 mol% and about 70 mol%, about 70 mol% to about 99.9 mol%, about 70 mol% to about 95 mol%, about 70 mol% to about 90 mol%, about 70 mol% to about 85 mol%, about 70 mol% to about 80 mol%, about 70 mol% to about 75 mol%, about 75 mol% to about 99.9 mol%, about 75 mol% to about 95 mol%, about 75 mol% to about 90 mol%, about 75 mol% to about 85 mol%, about 75 mol% to about 80 mol%, about 80 mol% to about 99.9 mol%, about 80 mol% to about 95 mol%, about 80 mol% to about 90 mol%, or about 80 mol% to about 85 mol%. In some embodiments, the sum of SiO2, B2O3, and Al2O3 is about 60 mol%, about 61 mol%, about 62 mol%, about 63 mol%, about 64 mol%, about 65 mol%, about 70 mol%, about 71 mol%, about 72 mol%, about 73 mol%, about 74 mol%, about 75 mol%, about 76 mol%, about 77 mol%, about 78 mol%, about 79 mol%, about 80 mol%, about 84 mol%, about 85 mol%, about 86 mol%, about 87 mol%, about 88 mol%, about 89 mol%, about 90 mol%, about 94 mol%, about 95 mol%, about 96 mol%, about 98 mol%, about 99 mol%, about 99.9 mol%, or any sum between these values.

[0046] According to some embodiments, the glass can include one or more alkaline earth oxides (RO), when present, where RO is CaO, MgO, BaO, and / or SrO. In some embodiments, the one or more alkaline earth oxides, individually or in combined amounts, can be between 0 mol% and about 15 mol%, between 0 mol% and about 12 mol%, between 0 mol% and about 10 mol%, between 0 mol% and about 8 mol%, between 0 mol% and about 5 mol%, between about 0.001 mol% and about 15 mol%, between about 0.001 mol% and about 12 mol%, between about 0.001 mol% and about 10 mol%, between about 0.001 mol% and about 8 mol%, between about 0.001 mol% and about 8.5 mol%, between about 0.001 mol% and about 5 mol%, between about 1 mol% and about 15 mol%, between about 0.0 ...5 mol%, between about 0.001 mol 5 mol%, about 1 mol% to about 12 mol%, about 1 mol% to about 10 mol%, about 1 mol% to about 8 mol%, about 1 mol% to about 8.5 mol%, about 1 mol% to about 5 mol%, about 2 mol% to about 15 mol%, about 2 mol% to about 12 mol%, about 2 mol% to about 10 mol%, about 2 mol% to about 8 mol%, about 2 mol% to about 8.5 mol%, about 2 mol% to about 5 mol%, about 5 mol% to about 15 mol%, about 5 mol% to about 12 mol%, about 5 mol% to about 10 mol%, or about 5 mol% to about 8 mol%. In some embodiments, one or more alkaline earth oxides are present, individually or in combined amounts, in an amount of 0 mol%, about 0.001 mol%, about 0.002 mol%, about 0.01 mol%, about 0.3 mol%, about 0.5 mol%, about 1 mol%, about 1.4 mol%, about 1.5 mol%, about 2 mol%, about 2.5 mol%, about 3 mol%, about 4 mol%, about 5 mol%, about 6 mol%, about 7 mol%, about 8 mol%, about 8.1 mol%, about 8.5 mol%, about 8.7 mol%, about 8.8 mol%, about 9 mol%, about 9.5 mol%, about 10 mol%, about 10.5 mol%, about 11 mol%, about 12 mol%, about 13 mol%, about 14 mol%, about 15 mol%, or any amount between these values.

[0047] In some implementations, the glass can include CaO and / or MgO, hi some embodiments, CaO is present in an amount between 0 mol% and about 10 mol% and MgO is present in an amount between 0 mol% and about 13 mol%. In some embodiments, CaO is present in an amount of 0 mol% to about 10 mol%, 0 mol% to about 9 mol%, 0 mol% to about 8 mol%, 0 mol% to about 6 mol%, 0 mol% to about 4 mol%, about 0.01 mol% to about 10 mol%, about 0.01 mol% to about 9 mol%, about 0.01 mol% to about 8 mol%, about 0.01 mol% to about 6 mol%, about 0.01 mol% to about 4 mol%, about 0.1 mol% to about 10 mol%, about 0.1 mol% to about 9 mol%, about 0.1 mol% to about 8 mol%, about 0.1 mol% to about 6 mol%, about 0.1 mol% to about 4 mol%, about 1 mol% to about 10 mol%, about 1 mol% to about 9 mol%, about 1 mol% to about 8 mol%, about 1 mol% to about 6 mol%, or about 1 mol% to about 4 mol%. For example, CaO can be present at 0 mol%, about 0.01 mol%, about 0.1 mol%, about 1 mol%, about 2 mol%, about 3 mol%, about 4 mol%, about 5 mol%, about 6 mol%, about 7 mol%, about 8 mol%, about 9 mol%, about 10 mol%, or any amount between these values. In some embodiments, MgO is from 0 mol% to about 13 mol%, 0 mol% to about 12 mol%, 0 mol% to about 10 mol%, 0 mol% to about 9 mol%, 0 mol% to about 8 mol%, 0 mol% to about 6 mol%, 0 mol% to about 4 mol%, about 0.01 mol% to about 13 mol%, about 0.01 mol% to about 12 mol%, about 0.01 mol% to about 10 mol%, about 0.01 mol% to about 9 mol%, about 0.01 mol% to about 8 mol%, about 0.01 mol% to about 6 mol%, about 0.01 mol% to about 4 mol%, %, about 0.1 mol % to about 13 mol %, about 0.1 mol % to about 12 mol %, about 0.1 mol % to about 10 mol %, about 0.1 mol % to about 9 mol %, about 0.1 mol % to about 8 mol %, about 0.1 mol % to about 6 mol %, about 0.1 mol % to about 4 mol %, about 1 mol % to about 13 mol %, about 1 mol % to about 12 mol %, about 1 mol % to about 10 mol %, about 1 mol % to about 9 mol %, about 1 mol % to about 8 mol %, about 1 mol % to about 6 mol %, or about 1 mol % to about 4 mol %.For example, MgO can be present at 0 mol%, about 0.01 mol%, about 0.1 mol%, about 1 mol%, about 2 mol%, about 3 mol%, about 4 mol%, about 5 mol%, about 6 mol%, about 7 mol%, about 8 mol%, about 9 mol%, about 10 mol%, about 11 mol%, about 12 mol%, about 13 mol%, or any amount between these values.

[0048] According to some embodiments of the present disclosure, the glass can include MgO and at least one additional alkaline earth oxide (RO) selected from CaO, BaO, and SrO. In some examples, the combination of MgO and the at least one additional RO can result in a glass having a lower dielectric constant and / or loss tangent compared to a glass containing MgO or another RO alone. In one embodiment, the total amount of MgO and the at least one additional RO (RO Total ) can be about 3 mol % to about 15 mol %. For example, RO Total can be about 3 mol% to about 15 mol%, about 3 mol% to about 12 mol%, about 3 mol% to about 10 mol%, about 3 mol% to about 8 mol%, about 3 mol% to about 6 mol%, about 4 mol% to about 15 mol%, about 4 mol% to about 12 mol%, about 4 mol% to about 10 mol%, about 4 mol% to about 8 mol%, about 4 mol% to about 6 mol%, about 5 mol% to about 15 mol%, about 3 mol% to about 12 mol%, about 5 mol% to about 10 mol%, about 5 mol% to about 8 mol%, about 6 mol% to about 15 mol%, about 6 mol% to about 12 mol%, about 6 mol% to about 10 mol%, about 6 mol% to about 8 mol%, about 8 mol% to about 15 mol%, about 8 mol% to about 12 mol%, or about 8 mol% to about 10 mol%. For example, RO Total can be about 3 mol%, about 4 mol%, about 5 mol%, about 6 mol%, about 7 mol%, about 8 mol%, about 9 mol%, about 10 mol%, about 11 mol%, about 12 mol%, about 13 mol%, about 14 mol%, about 15 mol%, or any amount between these values.

[0049] In some embodiments, the RO Total The ratio of MgO to RO (MgO:RO Total) is at least 0.3, at least 0.4, at least 0.5, at least 0.6, at least 0.7, or at least 0.8. For example, MgO:RO Total is about 0.3 to about 0.9, about 0.3 to about 0.8, about 0.3 to about 0.7, about 0.3 to about 0.6, about 0.3 to about 0.5, about 0.3 to about 0.4, about 0.4 to about 0.9, about 0.4 to about 0.8, about 0.4 to about 0.7, about 0.4 to about 0.6, about 0.4 to about 0.5, about 0.5 to about 0.9, about 0.5 to about 0.8, about 0.5 to about 0.7, about 0.5 to about 0.6, about 0.6 to about 0.9, about 0.6 to about 0.8, or about 0.6 to about 0.7. Total is about 0.3, about 0.31, about 0.36, about 0.38, about 0.4, about 0.42, about 0.44, about 0.45, about 0.48, about 0.49, about 0.5, about 0.59, about 0.6, about 0.63, about 0.69, about 0.7, about 0.8, about 0.86, about 0.9, or any ratio between these values.

[0050] According to one implementation, the at least one additional RO is CaO, the MgO is present in an amount between about 1 mol % and about 10 mol %, and the CaO is present in an amount between about 1 mol % and about 10 mol %. For example, MgO is present in an amount of about 1 mol% to about 10 mol%, about 2 mol% to about 10 mol%, about 3 mol% to about 10 mol%, about 4 mol% to about 10 mol%, about 5 mol% to about 10 mol%, about 1 mol% to about 8 mol%, about 2 mol% to about 8 mol%, about 3 mol% to about 8 mol%, about 4 mol% to about 8 mol%, about 5 mol% to about 8 mol%, about 1 mol% to about 7 mol%, about 2 mol% to about 7 mol%, about 3 mol% to about 7 mol%, about 4 mol% to about 7 mol%, about 5 mol% to about 7 mol%, about 1 mol% to about 5 mol%, about 2 mol% to about 5 mol%, about 3 mol% to about 5 mol%, or about 4 mol% to about 5 mol%, about 1 mol% about 1 mol%, about 2 mol% to about 10 mol%, about 3 mol% to about 10 mol%, about 4 mol% to about 10 mol%, about 5 mol% to about 10 mol%, about 1 mol% to about 8 mol%, about 2 mol% to about 8 mol%, about 3 mol% to about 8 mol%, about 4 mol% to about 8 mol%, about 5 mol% to about 8 mol%, about 1 mol% to about 7 mol%, about 2 mol% to about 7 mol%, about 3 mol% to about 7 mol%, about 4 mol% to about 7 mol%, about 5 mol% to about 7 mol%, about 1 mol% to about 5 mol%, about 2 mol% to about 5 mol%, about 3 mol% to about 5 mol%, or about 4 mol% to about 5 mol% of CaO.

[0051] According to one implementation, the at least one additional RO is SrO, the MgO is present in an amount between about 1 mol % and about 10 mol %, and the SrO is present in an amount between about 1 mol % and about 5 mol %. For example, MgO can be present in an amount of about 1 mol% to about 10 mol%, about 2 mol% to about 10 mol%, about 3 mol% to about 10 mol%, about 4 mol% to about 10 mol%, about 5 mol% to about 10 mol%, about 1 mol% to about 8 mol%, about 2 mol% to about 8 mol%, about 3 mol% to about 8 mol%, about 4 mol% to about 8 mol%, about 5 mol% to about 8 mol%, about 1 mol% to about 5 mol%, about 2 mol% to about 5 mol%, about 3 mol% to about 5 mol%, about 4 mol% to about 5 mol%, about 2 mol% to about 4 mol%, or about 3 mol% to about 4 mol% in any combination with SrO in an amount of about 1 mol% to about 5 mol%, about 2 mol% to about 5 mol%, about 3 mol% to about 5 mol%, about 4 mol% to about 5 mol%, about 2 mol% to about 4 mol%, or about 3 mol% to about 4 mol%.

[0052] In some embodiments, the amount of MgO and the amount of additional RO are as described above and the ratio of RO to Al2O3. Total Ratio of (RO Total The ratio R0:Al2O3 is selected so that the ratio R0 is greater than 1. Total By having Al2O3 greater than 1, it is possible to facilitate the formation of a manufacturable glass that can be drawn using conventional glass forming processes.

[0053] Without wishing to be bound by any theory, it is believed that for a glass derived from a precursor composition containing a single RO species, as the concentration of this single RO species decreases, the dielectric constant and loss tangent of the glass derived from said precursor composition, as measured using a 10 GHz signal, also decrease. Thus, for a given glass, by decreasing the concentration of a single RO species present in the glass, a lower dielectric constant and / or loss tangent can be achieved in the glass sample. Furthermore, for a given RO species, Total In terms of concentration, by combining MgO with at least one additional RO species such as CaO, SrO, and / or BaO, the RO Total It is believed that a reduced dielectric constant and / or loss tangent can be achieved in a glass sample compared to a glass derived from a precursor composition containing a similar concentration but only a single RO species. For example, a given RO Total In terms of concentration, glasses including combinations of MgO with CaO, SrO, and / or BaO according to the present disclosure can have a lower dielectric constant than glasses including only a single RO species selected from MgO, CaO, SrO, and BaO. Total With respect to concentration, glasses including combinations of MgO with CaO, SrO, and / or BaO according to the present disclosure can have a lower loss tangent than glasses including only a single RO species selected from CaO, SrO, and BaO.

[0054] In some embodiments, the amount of alkaline earth oxides in the glass can be selected in concert with other materials such as B2O3 and optionally Al2O3 to provide a glass with desired properties. For example, increasing the amount of alkaline earth oxides relative to SiO2 and Al2O3 can have the effect of lowering the viscosity of the glass melt, and can increase the melting point and forming temperature. Alkaline earth oxides can also increase the CTE and density of the glass, and can affect other properties such as the elastic modulus. Alkaline earth oxides can also lower the liquidus temperature. Thus, in some embodiments, the amount of alkaline earth oxides B2O3 and Al2O3 can be selected in accordance with the present disclosure to balance the desired physical properties and formability of the glass. In some implementations, the amount of alkaline earth oxides B2O3 and Al2O3 can be selected in accordance with the RO in the glass. Total In some embodiments, the ratio of RO:(Al2O3+(0.5*B2O3)) is selected to be about 0 to about 0.9. Total The ratio of (Al2O3+(0.5*B2O3)) is about 0 to about 0.9, about 0 to about 0.8, about 0 to about 0.7, about 0 to about 0.6, about 0 to about 0.5, about 0 to about 0.3, about 0.1 to about 0.9, about 0.1 to about 0.8, about 0.1 to about 0.7, about 0.1 to about 0.6, about 0.1 to about 0.5, about 0.2 to about 0.9, about 0.2 to about 0.8, about 0.2 to about 0.7, about 0.2 to about 0.6, about 0.2 to about 0.5, about 0.3 to about 0.9, about 0.3 to about 0.8, about 0.3 to about 0.7, about 0.3 to about 0.6, about 0.3 to about 0.5, about 0.4 to about 0.9, about 0.4 to about 0.8, about 0.4 to about 0.7, about 0.4 to about 0.6, about 0.1 to about 0.5, about 0.1 to about 0.4, about 0.1 to about 0.3, about 0.1 to about 0.2, about 0.2 to about 0.5, about 0.2 to about 0.4, about 0.2 to about 0.3, about 0.3 to about 0.5, about 0.3 to about 0.4, about 0.4 to about 0.5. In some embodiments, RO Total The ratio of: (Al2O3 + (0.5 * B2O3)) is about 0.1, about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, or any ratio between these values.

[0055] In some implementations, the amounts of alkaline earth oxides B2O3 and Al2O3 are adjusted to reduce the RO content in the glass. Total In some embodiments, the ratio of RO:(Al2O3+B2O3) is selected to be about 0.2 to about 0.6. Total The ratio of RO:(Al2O3+B2O3) is about 0.2 to about 0.6, about 0.2 to about 0.5, about 0.2 to about 0.4, about 0.3 to about 0.6, about 0.3 to about 0.5, about 0.3 to about 0.4, about 0.4 to about 0.6, about 0.4 to about 0.5, or about 0.5 to about 0.6. Total The ratio of Al2O3+B2O3 is about 0.2, about 0.24, about 0.25, about 0.28, about 0.29, about 0.3, about 0.32, about 0.35, about 0.36, about 0.4, about 0.5, about 0.55, about 0.58, about 0.6, or any ratio between these values.

[0056] In some embodiments, the glasses of the present disclosure have a viscosity of about 2.2 g / cm when measured at about 25° C. (approximately room temperature). 3 ~Approx. 2.5g / cm 3 For example, glass has a density of about 2.2 g / cm when measured at about 25°C (approximately room temperature). 3 ~Approx. 2.5g / cm 3 , about 2.3g / cm 3 ~Approx. 2.5g / cm 3 , about 2.4g / cm 3 ~Approx. 2.5g / cm 3 , about 2.2g / cm 3 ~ approx. 2.4g / cm 3 , about 2.3g / cm 3 ~ approx. 2.4g / cm 3 , or about 2.2 g / cm 3 ~Approx. 2.3g / cm 3 The density may be

[0057] Glasses of the present disclosure may optionally include one or more fining agents, such as, but not limited to, one or more halogen salts, including SnO2, Sb2O3, As2O3, and / or fluorine, chlorine, or bromine salts. If fining agents are present in the glass, they may be present in a total amount of less than about 1 mol%. In some embodiments, the fining agents are present in an amount of about 0.01 mol% to about 1 mol%, about 0.01 mol% to about 0.5 mol%, about 0.01 mol% to about 0.25 mol%, about 0.01 mol% to about 0.1 mol%, about 0.05 mol% to about 0.1 mol%, about 0.05 mol% to about 0.25 mol%, about 0.05 mol% to about 0.5 mol%, or about 0.05 mol% to about 1 mol%. In some embodiments, the fining agents are present in an amount of about 0.08 mol%, about 0.09 mol%, or about 0.1 mol%. If the content of the fining agent is too high, the fining agent may penetrate into the glass structure and affect various glass properties. However, if the content of the fining agent is too low, it may be difficult to mold the glass. According to one embodiment of the present disclosure, SnO2 is included as a fining agent in an amount of 0 mol% to about 0.3 mol%. For example, SnO2 may be present in an amount of 0 mol% to about 0.3 mol%, 0 mol% to about 0.2 mol%, 0 mol% to about 0.1 mol%, about 0.05 mol% to about 0.3 mol%, about 0.05 mol% to about 0.2 mol%, or about 0.05 mol% to about 0.1 mol%.

[0058] The glasses may optionally contain contaminants or unintentional additions, such as TiO2. If these additional materials are present, they are present only in very small or trace amounts, less than 0.2 mole percent.

[0059] In some implementations, the glass is substantially free of alkali metals. As used herein, the phrase "substantially free" is defined to mean that less than trace amounts of a material, in this case an alkali metal oxide, are present. Trace amounts of alkali metal oxide may be present due to contamination or manufacturing constraints. As noted above, in some implementations, the glasses of the present disclosure can be prepared without the addition of alkali metals such that the glass is substantially free of alkali metals to reduce the possibility of ion migration during processing. Reducing or minimizing the possibility of ion migration can be advantageous in some applications, such as when using the glass as a substrate for an electronic device where ion migration may be undesirable.

[0060] In some implementations, the glasses of the present disclosure can include at least one alkali metal oxide (RO), where RO is LiO, NaO, and / or KO. In some embodiments, the one or more alkali metal oxides are present, individually or in a combined amount, in an amount between 0 mol % and about 6 mol %. In some embodiments, the one or more alkali metal oxides may be, individually or in a combined amount, from 0 mol % to about 6 mol %, from 0 mol % to about 5 mol %, from 0 mol % to about 4 mol %, from 0 mol % to about 3 mol %, from 0 mol % to about 2 mol %, from about 0.0005 mol % to about 6 mol %, from about 0.0005 mol % to about 5 mol %, from about 0.0005 mol % to about 4 mol %, from about 0.0005 mol % to about 3 mol %, from about 0.0005 mol % to about 2 mol %, from about 0.001 mol % to about 6 mol %, from about 0.001 mol % to about 5 mol %, from about 0.001 mol % to about 4 mol %, or from about 0.001 mol %. about 0.01 mol% to about 3 mol%, about 0.001 mol% to about 2 mol%, about 0.01 mol% to about 6 mol%, about 0.01 mol% to about 5 mol%, about 0.01 mol% to about 4 mol%, about 0.01 mol% to about 3 mol%, about 0.01 mol% to about 2 mol%, about 0.1 mol% to about 6 mol%, about 0.1 mol% to about 5 mol%, about 0.1 mol% to about 4 mol%, about 0.1 mol% to about 3 mol%, about 0.1 mol% to about 2 mol%, about 1 mol% to about 6 mol%, about 1 mol% to about 5 mol%, about 1 mol% to about 4 mol%, about 1 mol% to about 3 mol%, or about 1 mol% to about 2 mol%. For example, Li2O can be present in an amount of 0 mol% to about 6 mol%, 0 mol% to about 5 mol%, 0 mol% to about 4 mol%, 0 mol% to about 3 mol%, about 0.1 mol% to about 6 mol%, about 0.1 mol% to about 5 mol%, about 0.1 mol% to about 4 mol%, about 0.1 mol% to about 3 mol%, about 1 mol% to about 6 mol%, about 1 mol% to about 5 mol%, about 1 mol% to about 4 mol%, or about 1 mol% to about 3 mol%. In another example, Na2O can be present in an amount of 0 mol% to about 0.05 mol%, 0 mol% to about 0.01 mol%, 0 mol% to about 0.005 mol%, 0 mol% to about 0.001 mol%, about 0.001 mol% to about 0.05 mol%, about 0.001 mol% to about 0.01 mol%, or about 0.001 mol% to about 0.005 mol%.In another example, KO can be present in an amount from 0 mol% to about 2 mol%, from 0 mol% to about 1 mol%, from 0 mol% to about 0.5 mol%, from about 0.1 mol% to about 2 mol%, from about 0.1 mol% to about 1 mol%, from about 0.1 mol% to about 0.5 mol%, from about 0.5 mol% to about 2 mol%, or from about 0.5 mol% to about 1 mol%.

[0061] In some embodiments, the glasses of the present disclosure have a dielectric constant D of about 10 or less when measured with a 10 GHz signal. k In some implementations, the glass has a dielectric constant D of about 10 or less, about 8 or less, about 7.5 or less, about 6 or less, about 5 or less, about 4 or less, or about 3 or less, when measured with a 10 GHz signal. k In some implementations, the glass has a dielectric constant D of about 2 to about 10, about 3 to about 10, about 4 to about 10, about 5 to about 10, about 6 to about 10, about 7 to about 10, about 8 to about 10, about 9 to about 10, about 2 to about 8, about 2 to about 6, about 2 to about 4, about 3 to about 10, about 3 to about 8, about 3 to about 6, about 3 to about 5, about 3 to about 4, about 4 to about 6, about 4 to about 8, or about 4 to about 10, when measured with a 10 GHz signal. k In some embodiments, the glass has a dielectric constant D of about 10, about 9, about 8, about 7, about 6, about 5, about 4.5, about 4, about 3.5, about 3, or any value between these values, when measured with a 10 GHz signal. k has.

[0062] In some embodiments, the glasses of the present disclosure can be characterized by a loss tangent of about 0.01 or less when measured with a 10 GHz signal. In some implementations, the glasses of the present disclosure are characterized by a loss tangent of about 0.01 or less, about 0.008 or less, about 0.005 or less, about 0.0025 or less, or about 0.001 or less when measured with a 10 GHz signal. In some embodiments, the glasses of the present disclosure are characterized by a loss tangent of from about 0.0004 to about 0.01, from about 0.001 to about 0.01, from about 0.0025 to about 0.01, from about 0.005 to about 0.01, from about 0.0004 to about 0.001, from about 0.0004 to about 0.0025, from about 0.0004 to about 0.005, from about 0.001 to about 0.0025, from about 0.001 to about 0.005, from about 0.0025 to about 0.005, from about 0.0004 to about 0.008, from about 0.001 to about 0.008, from about 0.0025 to about 0.008, or from about 0.005 to about 0.008, when measured with a 10 GHz signal. In some embodiments, the glasses of the present disclosure have a loss tangent, when measured with a 10 GHz signal, of about 0.0004, about 0.001, about 0.002, about 0.0025, about 0.003, about 0.004, about 0.005, about 0.006, about 0.007, about 0.008, or any value in between these values.

[0063] In some implementations, the glass has a dielectric constant D of about 10 or less, about 8 or less, about 7.5 or less, about 6 or less, about 5 or less, about 4 or less, or about 3 or less, all measured with a 10 GHz signal. k and a loss tangent of about 0.01 or less, about 0.008 or less, about 0.005 or less, about 0.0025 or less, or about 0.001 or less. For example, the glasses of the present disclosure have a relative dielectric constant D of about 2 to about 10, about 3 to about 10, about 4 to about 10, about 5 to about 10, about 6 to about 10, about 7 to about 10, about 8 to about 10, about 9 to about 10, about 2 to about 8, about 2 to about 6, about 2 to about 4, about 3 to about 10, about 3 to about 8, about 3 to about 6, about 3 to about 5, about 3 to about 4, about 4 to about 6, about 4 to about 8, or about 4 to about 10, all measured with a 10 GHz signal. kand a loss tangent of about 0.0004 to about 0.01, about 0.001 to about 0.01, about 0.0025 to about 0.01, about 0.005 to about 0.01, about 0.0004 to about 0.001, about 0.0004 to about 0.0025, about 0.0004 to about 0.005, about 0.001 to about 0.0025, about 0.001 to about 0.005, about 0.0025 to about 0.005, about 0.0004 to about 0.008, about 0.001 to about 0.008, about 0.0025 to about 0.008, or about 0.005 to about 0.008. In some examples, the glasses of the present disclosure have a dielectric constant of about 10 or less and a loss tangent of about 0.01 or less, both measured with a 10 GHz signal. In other examples, the glasses of the present disclosure have a dielectric constant of about 7.5 or less and a loss tangent of about 0.005 or less, both measured with a 10 GHz signal, or a dielectric constant of about 5 or less and a loss tangent of about 0.005 or less, both measured with a 10 GHz signal. In some examples, the glasses of the present disclosure have a dielectric constant of about 10 or less and a loss tangent of about 0.008 or less, both measured with a 10 GHz signal.

[0064] According to one aspect of the present disclosure, the glasses of the present disclosure can have a CTE that facilitates the formation of glass laminates using a downdraw process such as fusion draw. As discussed above, the laminate fusion draw process employs two isopipes to form a laminate sheet that includes a core composition surrounded on one or both sides by an outer cladding layer. For example, the glasses of the present disclosure can have a CTE of about 31×10 -7 / °C. In another example, the glasses of the present disclosure can be used as cladding, where the core glass layer has a higher CTE, such that there is a CTE mismatch between the core glass layer and the cladding layer, where the CTE of the cladding is equal to or less than the CTE of the core. Such a CTE mismatch can result in the formation of compressive stresses in the outer regions of the glass sheet and tensile stresses in the inner regions of the glass sheet upon cooling, thereby strengthening the glass. One example of a high CTE glass is 84×10 -7 / °C.

[0065] In some embodiments, the glasses of the present disclosure are characterized by a relatively low CTE, which can be beneficial in cladding layers for glass laminates, where the cladding layers have a lower CTE than the core layer, and in other implementations. In some embodiments, the glasses of the present disclosure also have a CTE of about 25×10 when measured between 0° C. and 300° C. -7 / ℃ ~ approx. 65×10 -7 / °C. In some embodiments, the glasses of the present disclosure have an average CTE of about 25×10 / °C when measured from 25°C to 300°C. -7 / ℃ ~ approx. 60×10 -7 / ℃, approx. 25×10 -7 / ℃ ~ approx. 55×10 -7 / ℃, approx. 25×10 -7 / ℃ ~ approx. 50×10 -7 / ℃, approx. 25×10 -7 / ℃ ~ approx. 45×10 -7 / ℃, approx. 25×10 -7 / ℃ ~ approx. 40×10 -7 / ℃, approx. 25×10 -7 / ℃ ~ approx. 35×10 -7 / ℃, approx. 25×10 -7 / ℃ ~ approx. 30×10 -7 / ℃, approx. 30×10 -7 / ℃ ~ approx. 65×10 -7 / ℃, approx. 30×10 -7 / ℃ ~ approx. 60×10 -7 / ℃, approx. 30×10 -7 / ℃ ~ approx. 55×10 -7 / ℃, approx. 30×10 -7 / ℃ ~ approx. 50×10 -7 / ℃, approx. 30×10 -7 / ℃ ~ approx. 30×10 -7 / ℃, approx. 30×10 -7 / ℃ ~ approx. 40×10 -7 / ℃, approx. 30×10 -7 / ℃ ~ approx. 35×10 -7 / ℃, approx. 35×10 -7 / ℃ ~ approx. 65×10 -7 / ℃, approx. 35×10 -7 / ℃ ~ approx. 60×10 -7 / ℃, approx. 35×10 -7 / ℃ ~ approx. 55×10 -7 / ℃, approx. 35×10-7 / ℃ ~ approx. 50×10 -7 / ℃, approx. 35×10 -7 / ℃ ~ approx. 45×10 -7 / ℃, approx. 35×10 -7 / ℃ ~ approx. 40×10 -7 / ℃, approx. 40×10 -7 / ℃ ~ approx. 65×10 -7 / ℃, approx. 40×10 -7 / ℃ ~ approx. 60×10 -7 / ℃, approx. 40×10 -7 / ℃ ~ approx. 55×10 -7 / ℃, approx. 40×10 -7 / ℃ ~ approx. 50×10 -7 / ℃, approx. 40×10 -7 / ℃ ~ approx. 45×10 -7 / ℃, approx. 50×10 -7 / ℃ ~ approx. 60×10 -7 / ℃, approx. 50×10 -7 / ℃ ~ approx. 55×10 -7 / ℃, approx. 50×10 -7 / ℃ ~ approx. 65×10 -7 / ℃, approx. 55×10 -7 / ℃ ~ approx. 60×10 -7 / °C, or approximately 55 x 10 -7 / ℃ ~ approx. 65×10 -7 In some embodiments, the glasses of the present disclosure are characterized by a CTE of about 28×10 / ° C. when measured from 25° C. to 300° C. -7 / ℃, 29×10 -7 / ℃, 30×10 -7 / ℃, 31×10 -7 / ℃, 32×10 -7 / ℃, 33×10 -7 / ℃, 34×10 -7 / ℃ or 35×10 -7 / °C CTE.

[0066] In some implementations, the glasses of the present disclosure can also be characterized by a liquidus viscosity of about 40 kpoise to about 5000 kpoise. In some embodiments, the glasses of the present disclosure can have a liquidus viscosity of about 40 kpoise to about 3000 kpoise, about 40 kpoise to about 2000 kpoise, about 40 kpoise to about 1000 kpoise, about 40 kpoise to about 800 kpoise, about 40 kpoise to about 600 kpoise, about 40 kpoise to about 400 kpoise, about 40 kpoise to about 300 kpoise, about 40 kpoise to about 250 kpoise, about 40 kpoise to about 200 kpoise, about 40 kpoise to about 100 kpoise, about 100 kpoise to about 500 kpoise, or about 500 kpoise to about 500 kpoise. The liquidus viscosity of the composition is about 100 kpoise, about 100 kpoise to about 400 kpoise, about 100 kpoise to about 300 kpoise, about 100 kpoise to about 200 kpoise, about 200 kpoise to about 300 kpoise, about 200 kpoise to about 400 kpoise, about 200 kpoise to about 500 kpoise, about 200 kpoise to about 5000 kpoise, about 200 kpoise to about 3000 kpoise, about 200 kpoise to about 2000 kpoise, or about 200 kpoise to about 1000 kpoise.

[0067] In some implementations, the glasses of the present disclosure can also be characterized by a 35,000 poise temperature of about 1110° C. to about 1325° C. In some embodiments, the 35,000 poise temperature is about 1110° C. to about 1300° C., about 1110° C. to about 1250° C., about 1110° C. to about 1200° C., about 1200° C. to about 1325° C., about 1250° C. to about 1325° C., about 1300° C. to about 1325° C., about 1200° C. to about 1300° C., about 1200° C. to about 1250° C., or about 1250° C. to about 1300° C. In some embodiments, the 35,000 poise temperature of the glasses of the present disclosure is about 1120° C., about 1180° C., about 1190° C., about 1200° C., or about 1250° C.

[0068] In some implementations, the glasses of the present disclosure can also be characterized as having a 200 poise melting point of about 1600° C. to about 1800° C., about 1600° C. to about 1750° C., about 1600° C. to about 1700° C., about 1600° C. to about 1650° C., 1640° C. to about 1825° C., 1640° C. to about 1800° C., about 1640° C. to about 1750° C., about 1640° C. to about 1700° C., about 1600° C. to about 1750° C., about 160 ... 40°C to about 1675°C, about 1675°C to about 1825°C, about 1675°C to about 1800°C, about 1675°C to about 1750°C, about 1675°C to about 1700°C, about 1700°C to about 1825°C, about 1700°C to about 1800°C, about 1700°C to about 1750°C, about 1750°C to about 1825°C, or about 1750°C to about 1800°C. In some embodiments, the 200 poise melting point is about 1660°C, about 1670°C, about 1680°C, about 1690°C, about 1700°C, or about 1800°C.

[0069] In some implementations, the glasses of the present disclosure are suitable for use in printed circuit board (PCB) applications. PCB laminates typically include an insulating layer laminated to a copper film, the insulating layer being disposed between copper clad films. The insulating layer preferably has low dielectric loss, e.g., less than 0.005 at 10 GHz, and sufficient mechanical strength and fracture toughness to allow handling and post-processing in a manufacturing environment. The insulating layer must also be able to withstand via / hole drilling without breaking or fracturing, and can have a thickness of about 100 to 700 micrometers, depending on the application.

[0070] Additionally, the insulating layer is preferably capable of withstanding temperatures of up to 260° C. for 30 seconds while maintaining dimensional stability. This temperature is typically based on the temperature required for solder reflow in later processing of PCB boards. Solder paste is typically used to attach electronic components to their contact pads. The assembly is then exposed to high temperatures (typically 260° C. for 30 seconds), which causes the solder to reflow and form permanent solder joints. Thus, the insulating layer of the PCB is preferably a low dielectric loss material that can withstand the solder reflow temperatures typically used in PCB processing with little or no softening or dimensional change.

[0071] There are several commercially available materials that are used as insulating layers in PCBs. For example, one common glass / epoxy laminate used as an insulating layer in PCB applications has a loss tangent of 0.0058 at a signal frequency of 10 GHz. However, as the industry moves to higher and higher signal frequencies, this insulating laminate has limited loss tangents. Other laminates, such as fused silica / polymer laminates, have been shown to exhibit low loss characteristics at frequencies above 10 GHz, but the mechanical properties of the fused silica and polymer layers limit the use of this laminate in some processes because the fused silica layer can crack during post-processing.

[0072] According to one embodiment, the glass of the present disclosure can be suitable for use as an insulating layer in PCB applications.The glass of the present disclosure features dielectric properties such as low dielectric constant and low loss tangent at 10 GHz signal frequencies, which are desirable as the industry moves to higher signal frequencies.When the glass of the present invention is utilized in combination with a polymer film that also has a low loss tangent to form an insulating laminate, the overall loss tangent of the PCB laminate can be much lower.

[0073] In some implementations, the glasses of the present disclosure can be characterized by dimensional stability suitable for use in PCB applications. As used herein, "dimensional stability" is defined as dimensional stability for 30 seconds when heated at 260°C. As mentioned above, typical PCB processing involves solder reflow temperatures around 260°C. The glasses of the present disclosure can be characterized by a softening point significantly higher than 260°C, which is an indication of the dimensional stability of the glass at temperatures typically encountered in PCB solder reflow processes. One example for determining the dimensional stability of the glass includes determining the length, width, thickness, weight, volume, and / or density of pre-cut samples prior to heating the samples in an oven preheated to 260°C. After heating the samples for 30 seconds, they can be removed. After cooling back to room temperature, the length, width, thickness, weight, volume, and / or density of the samples can be determined and compared to the values ​​obtained for each sample prior to heating to determine the relative change in each parameter.

[0074] Unless otherwise specified, glasses according to the present disclosure are prepared by mixing powder batches of the components (also referred to as glass precursor compositions) in a turbula for 60 minutes and melting them in a jacketed platinum crucible at 1650°C for 16 hours. The molten glass is then poured out as a block and annealed at 550-600°C. As will be appreciated by those skilled in the art, during melting of the components, various melting components (e.g., fluorine, alkali metals, boron, etc.) may be subject to different levels of volatilization (e.g., as a function of vapor pressure, melting time, and / or melting temperature), which may lead to differences in component content between the as-batched composition (i.e., the glass precursor composition from which the glass is derived) and the final glass article. Thus, the term "about" with respect to such components is intended to encompass values ​​within about 1 mole % when measured in the final article as compared to the as-batched compositions provided herein. It is understood that it is within the scope of the present disclosure to form glasses from the as-batch compositions described herein using different processes and / or process parameters, and that such differences in the processing of the as-batch compositions may lead to different levels of volatilization during melting of the components.

[0075] Exemplary glass composition A for a glass of the present disclosure according to certain embodiments of the present disclosure is shown below in Table 1. Table 1 identifies combinations of materials according to the present disclosure and the amount of each material as a range. Exemplary glass composition A in Table 1 may include additional components according to any embodiment of the present disclosure described herein.

[0076] [Table 1]

[0077] Exemplary glass composition B for glasses of the present disclosure according to certain embodiments of the present disclosure is shown below in Table 2. Table 2 identifies combinations of materials according to the present disclosure and the amounts of each material as ranges. Exemplary glass composition B in Table 2 may include additional components according to any embodiment of the present disclosure described herein.

[0078] [Table 2]

[0079] In some implementations, glasses made from exemplary glass compositions A and / or B according to Tables 1 and 2, respectively, have a dielectric constant of about 0.01 or less, about 0.008 or less, about 0.01 or less, about 0.020 or less, about 0.025 or less, about 0.030 or less, about 0.040 or less, about 0.050 or less, about 0.060 or less, about 0.070 or less, about 0.080 or less, about 0.090 or less, about 0.100 or less, about 0.150 or less, about 0.200 or less, about 0.250 or less, about 0.300 or less, about 0.400 or less, about 0.400 or less, about 0.500 or less, about 0.600 or less, about 0.700 or less, about 0.800 or less, about 0.9 ... in combination with a loss tangent of 0.005 or less, about 0.0025 or less, about 0.001 or less, about 0.0004 to about 0.01, about 0.001 to about 0.01, about 0.0025 to about 0.01, about 0.005 to about 0.01, about 0.0004 to about 0.001, about 0.0004 to about 0.0025, about 0.0004 to about 0.005, about 0.001 to about 0.0025, about 0.001 to about 0.005, about 0.0025 to about 0.005, about 0.0004 to about 0.008, about 0.001 to about 0.008, about 0.0025 to about 0.008, or about 0.005 to about 0.008.

[0080] In addition, the glasses derived from the exemplary glass compositions A and / or B in Tables 1 and 2, respectively, have a melting point of about 25×10 -7 / ℃ ~ approx. 65×10 -7 / ℃, approx. 25×10 -7 / ℃ ~ approx. 60×10 -7 / ℃, approx. 25×10 -7 / ℃ ~ approx. 55×10 -7 / ℃, approx. 25×10-7 / ℃ ~ approx. 50×10 -7 / ℃, approx. 25×10 -7 / ℃ ~ approx. 45×10 -7 / ℃, approx. 25×10 -7 / ℃ ~ approx. 40×10 -7 / ℃, approx. 25×10 -7 / ℃ ~ approx. 35×10 -7 / ℃, approx. 25×10 -7 / ℃ ~ approx. 30×10 -7 / ℃, approx. 30×10 -7 / ℃ ~ approx. 65×10 -7 / ℃, approx. 30×10 -7 / ℃ ~ approx. 60×10 -7 / ℃, approx. 30×10 -7 / ℃ ~ approx. 55×10 -7 / ℃, approx. 30×10 -7 / ℃ ~ approx. 50×10 -7 / ℃, approx. 30×10 -7 / ℃ ~ approx. 30×10 -7 / ℃, approx. 30×10 -7 / ℃ ~ approx. 40×10 -7 / ℃, approx. 30×10 -7 / ℃ ~ approx. 35×10 -7 / ℃, approx. 35×10 -7 / ℃ ~ approx. 65×10 -7 / ℃, approx. 35×10 -7 / ℃ ~ approx. 60×10 -7 / ℃, approx. 35×10 -7 / ℃ ~ approx. 55×10 -7 / ℃, approx. 35×10 -7 / ℃ ~ approx. 50×10 -7 / ℃, approx. 35×10 -7 / ℃ ~ approx. 45×10 -7 / ℃, approx. 35×10 -7 / ℃ ~ approx. 40×10 -7 / ℃, approx. 40×10 -7 / ℃ ~ approx. 65×10 -7 / ℃, approx. 40×10 -7 / ℃ ~ approx. 60×10 -7 / ℃, approx. 40×10 -7 / ℃ ~ approx. 55×10 -7 / ℃, approx. 40×10 -7 / ℃ ~ approx. 50×10 -7 / ℃, approx. 40×10 -7 / ℃ ~ approx. 45×10 -7 / ℃, approx. 50×10 -7 / ℃ ~ approx. 60×10 -7 / ℃, approx. 50×10 -7 / ℃ ~ approx. 55×10 -7 / ℃, approx. 50×10 -7 / ℃ ~ approx. 65×10 -7 / ℃, approx. 55×10 -7 / ℃ ~ approx. 60×10 -7 / °C, or approximately 55 x 10 -7 / ℃ ~ approx. 65×10 -7 It may be further characterized by an average CTE in °C / °C.

[0081] Additionally, glasses derived from exemplary glass compositions A and / or B according to Tables 1 and 2, respectively, may be further characterized by dimensional stability at 260° C. for 30 seconds.

[0082] In some implementations, the glasses from exemplary glass compositions A and / or B according to Tables 1 and 2, respectively, have a melting point of about 40 kpoise to about 5000 kpoise, about 40 kpoise to about 3000 kpoise, about 40 kpoise to about 2000 kpoise, about 40 kpoise to about 1000 kpoise, about 40 kpoise to about 800 kpoise, about 40 kpoise to about 600 kpoise, about 40 kpoise to about 400 kpoise, about 40 kpoise to about 300 kpoise, about 40 kpoise to about 250 kpoise, about 40 kpoise to about 200 kpoise, about 40 kpoise to about 50 ...5000 kpoise, about 40 kpoise to about 5000 kpoise, about 40 kpoise to about 5000 kpoise, about 40 kpoise to about 600 kpoise, about 40 kpoise to about 600 kpoise, about 40 kpoise to about 5000 kpoise, about 40 kpoise to about 5000 kpoise, about 40 kpoise to about 600 kpoise, about 40 k The liquidus viscosity may be from about 100 kpoise to about 100 kpoise, from about 100 kpoise to about 500 kpoise, from about 100 kpoise to about 400 kpoise, from about 100 kpoise to about 300 kpoise, from about 100 kpoise to about 200 kpoise, from about 200 kpoise to about 300 kpoise, from about 200 kpoise to about 400 kpoise, from about 200 kpoise to about 500 kpoise, from about 200 kpoise to about 5000 kpoise, from about 200 kpoise to about 3000 kpoise, from about 200 kpoise to about 2000 kpoise, or from about 200 kpoise to about 1000 kpoise.

[0083] In some implementations, the glasses derived from exemplary glass compositions A and / or B according to Tables 1 and 2, respectively, may be further characterized by a 35,000 poise temperature of about 1110° C. to about 1325° C. In some embodiments, the 35,000 poise temperature is about 1110° C. to about 1300° C., about 1110° C. to about 1250° C., about 1110° C. to about 1200° C., about 1200° C. to about 1325° C., about 1250° C. to about 1325° C., about 1300° C. to about 1325° C., about 1200° C. to about 1300° C., about 1200° C. to about 1250° C., or about 1250° C. to about 1300° C. In some embodiments, the 35,000 poise temperature of the glasses of the invention is about 1120°C, about 1180°C, about 1190°C, about 1200°C, or about 1250°C.

[0084] In some implementations, the glasses derived from exemplary glass compositions A and / or B according to Tables 1 and 2, respectively, may be further characterized by a 200 poise melting point of about 1600° C. to about 1825° C. In some embodiments, the 200 poise melting point of the glasses of the invention is about 1600° C. to about 1800° C., about 1600° C. to about 1750° C., about 1600° C. to about 1700° C., about 1600° C. to about 1650° C., 1640° C. to about 1825° C., about 1640° C. to about 1800° C., about 1640° C. to about 1750° C., about 1640° C. to about 1700° C., about ...700° C., about 1640° C. to about 1700° C., about 1640° C. to about 1700° C., about 164 40°C to about 1675°C, about 1675°C to about 1825°C, about 1675°C to about 1800°C, about 1675°C to about 1750°C, about 1675°C to about 1700°C, about 1700°C to about 1825°C, about 1700°C to about 1800°C, about 1700°C to about 1750°C, about 1750°C to about 1825°C, or about 1750°C to about 1800°C. In some embodiments, the 200 poise melting point is about 1660°C, about 1670°C, about 1680°C, about 1690°C, about 1700°C, or about 1800°C.

[0085] According to another aspect of the present disclosure, the composition of an exemplary glass according to the present disclosure can be defined by a convex hull, where the boundary points of the convex hull are based on the sum of oxides present in the glass. The convex hull of a set of N points in Euclidean space is the smallest convex set that contains the N points. The boundary points of the convex hull can be expressed as coordinates of a three-dimensional Cartesian coordinate system having an origin 0 and X, Y, and Z coordinate axes. In the present disclosure, the N points defining the convex hull are based on the concentrations of 15 oxides present in the exemplary glass according to the present disclosure for which experimental dielectric constant and loss tangent data were obtained. The boundary points of the convex hull are based on the composition of an exemplary glass according to the present disclosure that exhibited the desired dielectric properties, in this case a dielectric constant of 10 or less and a loss tangent of 0.008 or less when measured with a 10 GHz signal. The convex hull for the present disclosure was based on experimental data for 37 exemplary glasses shown in Table 3 below. Table 3 shows exemplary glasses according to the present disclosure ("EG") in mole percent calculated on an oxide basis from the as-batched glasses (i.e., glass precursor compositions) and the dielectric constants (D k ) and loss tangent measurements. The 15 oxides used to define the convex hull for the exemplary glasses of the present disclosure include: SiO2, Al2O3, B2O3, Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, SnO2, ZnO, La2O3, F, and Fe2O3. These 15 oxides were divided into three groups. The sum of the amount of oxide in each group represents one of the coordinates of the boundary point that defines the convex hull. The "X" coordinate of the boundary point of the convex hull is the first sum (X sum The "Y" coordinates of the boundary points of the convex hull can be based on a second sum (Y sum The "Z" coordinate of the boundary points of the convex hull can be based on a third sum (Z sum). The individual amount of any one of the components for each boundary point can be 0 (i.e., that particular component is not added to the composition). The sum of the X, Y, and Z coordinates for each boundary point equals 100.

[0086] [Table 3-1]

[0087] [Table 3-2]

[0088] According to certain aspects of the present disclosure, an exemplary glass may be derived from exemplary glass composition C, having components that fill a convex hull defined by the boundary points identified in Table 4, and exhibiting a dielectric constant of about 10 or less and / or a loss tangent of about 0.008 or less as measured with a 10 GHz signal. The glass compositions of Table 4 may include additional components according to any aspect of the present disclosure described herein.

[0089] [Table 4]

[0090] The boundary points in Table 4 are based on grouping the oxides as shown in Table 4 to provide respective X, Y, and Z coordinates. However, while still defining exemplary glass composition C, the X, Y, and Z coordinates for each boundary point of the convex hull of exemplary glass composition C can also be represented by different groupings of oxides, which may be expressed as X, Y, and Z coordinates for each boundary point of the convex hull of exemplary glass composition C. sum , Y sum , and Z sum This results in different values ​​for

[0091] FIG. 2 is a two-dimensional plot of the X and Y coordinates of the convex hull defined by the boundary points of the convex hull of exemplary glass composition C of Table 4.

[0092] According to another aspect of the disclosure, an exemplary glass may be derived from exemplary glass composition D, having components that fill a convex hull defined by the boundary points identified in Table 5, and exhibiting a dielectric constant of about 10 or less and / or a loss tangent of about 0.008 or less as measured with a 10 GHz signal. The glass compositions of Table 5 may include additional components according to any aspect of the disclosure described herein.

[0093] [Table 5]

[0094] The boundary points in Table 5 are based on grouping the oxides as shown in Table 5 to provide respective X, Y, and Z coordinates. However, while still defining exemplary glass composition D, the X, Y, and Z coordinates for each boundary point of the convex hull of exemplary glass composition D can also be represented by different groupings of oxides, which may be expressed as X, Y, and Z coordinates for each boundary point of the convex hull of exemplary glass composition D. sum , Y sum , and Z sum This results in different values ​​for

[0095] FIG. 3 is a two-dimensional plot of the X and Y coordinates of the convex hull defined by the boundary points of the convex hull of exemplary glass composition D in Table 5.

[0096] The X, Y, and Z coordinates of the boundary points of the convex hull of Tables 4 and 5 correspond to the sum of the amounts of a number of oxides. In some examples, one or more of these oxides may not be added to the glass composition (i.e., the composition may be substantially free of the particular oxide), and thus the concentration of the particular oxide will be "0" for purposes of determining the value of the coordinate. In one example, the glass is substantially free of F, La2O3, and / or ZnO. In this case, when determining the value of the Z coordinate of the boundary points for the convex hull of Table 4 or Table 5, the value "0" would be entered for the oxides not added to the composition. According to another aspect of the present disclosure, the exemplary glass includes F, La2O3, and / or ZnO. In some aspects, the exemplary glass includes an alkali metal oxide (RO). In some embodiments, the exemplary glass can include at least MgO from the group of Li2O, Na2O, KO, MgO, CaO, SrO, and BaO, and at least ZnO from the group of SnO2, ZnO, La2O3, F, and Fe2O3. In some embodiments, the exemplary glass can include at least one of CaO and BaO from the group of Li2O, Na2O, KO, MgO, CaO, SrO, and BaO, and at least SnO2 from the group of SnO2, ZnO, La2O3, F, and Fe2O3.

[0097] One method for determining whether a composition is within the convex hull defined by the boundary points of Table 4 or Table 5 utilizes MATLAB® from MathWorks®. To determine whether a test composition is within the convex hull of Table 4 or Table 5, the components of the test composition ("P") are projected into a reduced space having coordinates as follows: the "X" coordinate is the sum of the amounts of SiO2, Al2O3, and B2O3 (X sum ) and the "Y" coordinate is the sum of the amounts of Li2O, Na2O, KO, MgO, CaO, SrO, and BaO (Y sum ), and the "Z" coordinate is the sum of the amounts of SnO2, ZnO, La2O3, F, and Fe2O3 (Z sum) (mole percent of oxides). Depending on which convex hull is being tested, the boundary points from Table 4 or Table 5 can be input into the software as set "K". The appropriate MATLAB code for testing the convex hull can be executed, which in MATLAB version R2019a is the code "inhul(P,K)" (it is understood that the code for testing the convex hull may vary depending on the version and / or software). If the response is "0", then the point corresponding to the test composition P is not within the convex hull space bounded by K (which is the space defined by the boundary points of Table 4 or Table 5). If the software response is "1", then the point corresponding to the test composition P is within the convex hull space bounded by K, such that the test composition P is within the range of exemplary glass precursor compositions of the convex hull being tested (i.e., the convex hull defined by the boundary points of Table 4 or Table 5). A data point is determined to be bounded by a convex hull if the data point is within the space defined by the convex hull or on the boundary line of the convex hull.

[0098] For example, the (X sum , Y sum , Z sum ) coordinates are (73.72, 20.66, 5.31), which represents a point that is within the convex hull defined by the boundary points in Table 4. sum , Y sum , Z sum ) coordinates are (93.65, 6.15, 0.12), which represents a point that is within the convex hull defined by the boundary points in Table 4. For example, the (X sum , Y sum , Z sum ) coordinates are (78.41, 21.13, 0.121), which represents a point that is within the convex hull defined by the boundary points in Table 5. sum , Y sum , Z sum ) coordinates are (92.36, 7.55, 0.091), which represents a point that is within the convex hull defined by the boundary points in Table 5.

[0099] According to another aspect of the disclosure, an exemplary glass is defined by a convex hull of exemplary glass composition C of Table 4 and / or exemplary glass composition D of Table 5, and has the following formulas 1 and 2 (in mole percent of oxides): -42.8440902+0.463763055*[SiO2]+0.520077325*[Al2O3]+0.468168738 *[B2O3]+0.47253232*[Li2O]+2.11958583*[K2O]+0.499421381*[MgO]+0. 558094225*[CaO]+0.805792958*[SrO]+0.637349469*[BaO]-0.17232118* [SnO2]+0.525853343*[ZnO]+0.261394654*[La2O3]+0.469279089*[F]≦10 formula 1 and 0.756212572817506+[K2O]+0.209148876828416*[La2O3]+0.0884393206156657*[BaO]+0.0384462744417 211*[CaO]+(5.95212630529679-[F]) / [B2O3]+(254.196472343803-2.1615185467817*[B2O3]) / [SiO2]≦10 formula 2 The glass composition may be derived from a glass composition that satisfies at least one of the following criteria:

[0100] Equations 1 and 2 show the relative dielectric constant D at a 10 GHz signal for several example glasses of the present disclosure. kThe data was obtained by analyzing measurements of the dielectric constant of the glass precursor composition defined by the convex hull of Table 4 and / or Table 5. Equation 1 and / or Equation 2 can be used to predict which of the glass precursor compositions defined by the convex hull of Table 4 and / or Table 5 can be formed into glasses having a dielectric constant of 10 or less when measured with a 10 GHz signal. The data was analyzed using linear regression or a genetic algorithm to determine a model for the measured dielectric constant of the glass, along with the concentration (in mole percent of the oxide) of 15 predetermined oxides in the glass precursor composition from which the glass was derived. The 15 predetermined oxides were: SiO2, Al2O3, B2O3, Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, SnO2, ZnO, La2O3, F, and Fe2O3.

[0101] To develop the dielectric constant model, experimental data was obtained for 37 glasses that had a dielectric constant of 10 or less when measured with a 10 GHz signal. The oxide concentrations in the precursor compositions used to form these glasses, as well as the dielectric constant D of the formed glass for each of these 37 examples, were used to develop the dielectric constant model. k The measured values ​​of dielectric constant and loss tangent are shown in Table 3 above. The experimental data were divided into a teacher group (EG2-EG4, EG6-EG25, and EG37-EG38) and a test group (EG5 and EG26-EG36). The teacher group was used to develop models using linear regression or genetic algorithms, and the test group was used to test the validity of the models. The coefficient of determination (R 2 " ) and the predicted dielectric constant for this particular exemplary glass, a model fit was determined.

[0102] Equation 1 was determined using a linear regression analysis of approximately half of the examples in Table 3 (the teacher group). Figure 4 is a plot of the predicted dielectric constant for the remaining examples (the test group) based on Equation 1 compared to the measured dielectric constant for each example in the test group. The data points in Figure 4 correspond to the individual examples in Table 3, and the dotted lines represent a least-squares regression fit to the data points. The R in Equation 1 2The value was 0.9923, indicating a good fit between the predicted and measured dielectric constants for the test set examples.

[0103] Equation 2 was determined using a genetic algorithm framework and had an R of at least 0.9. 2 A nonlinear random function was evolved over many generations, with hundreds of iterations in each generation, until multiple functions with values ​​were found. The genetic algorithm generates a population of points in each iteration, and the points for each iteration are generated using a random number generator. Equation 2 is expressed as R 2 was selected from the list of generated functions based on the value and the number of fitting parameters of the generated function (i.e., R 2 (The R value is a measure of the accuracy of the function; the simpler the function, the smaller the fitting parameters.) Figure 5 is a plot of the predicted dielectric constant for the remaining half of the examples (the test set) based on Equation 2 compared to the measured dielectric constant for each example in the test set. 2 The value was 0.9931, indicating a good fit between the predicted and measured dielectric constants for glass.

[0104] To determine whether the test precursor composition satisfies Equation 1 and / or Equation 2, the above equations are solved using the corresponding oxide concentrations in the precursor composition. If the solved equations output a value less than or equal to 10, the test precursor composition satisfies the above equations. If the solved equations output a value greater than 10, the test precursor composition does not satisfy the above equations. With respect to Equations 1 and 2, a good fit between the predicted dielectric constants and the measured dielectric constants for the test set of examples indicates at least a reasonable expectation to use Equation 1 and / or 2 to predict whether a composition will have a dielectric constant less than or equal to 10 when measured at 10 GHz.

[0105] If a glass composition is defined by the convex hull of Table 4 and / or Table 5 and does not satisfy either Equation 1 or Equation 2, then a glass derived from that particular precursor composition is unlikely to have a dielectric constant of 10 or less when measured with a 10 GHz signal, and therefore the glass would not be included in the glasses of the present disclosure. If a glass composition is defined by the convex hull of Table 4 and / or Table 5 and satisfies both Equation 1 and Equation 2, then such a glass is likely to have a dielectric constant of 10 or less when measured with a 10 GHz signal, and therefore falls within the scope of the exemplary glasses of the present disclosure. If a glass composition is defined by the convex hull of Table 4 and / or Table 5 and satisfies only one of Equation 1 and Equation 2, then such a glass is likely to have a dielectric constant of 10 or less when measured with a 10 GHz signal, and therefore falls within the scope of the exemplary glasses of the present disclosure. Glasses derived from compositions satisfying Equation 1 and / or Equation 2 can have a measured dielectric constant of about 10 or less, about 8 or less, about 7.5 or less, about 5 or less, about 4 or less, or about 3 or less, when measured with a 10 GHz signal. In some implementations, glasses derived from compositions satisfying Equation 1 and / or Equation 2 can have a measured dielectric constant of about 2 to about 10, about 3 to about 10, about 4 to about 10, about 5 to about 10, about 6 to about 10, about 7 to about 10, about 8 to about 10, about 9 to about 10, about 2 to about 8, about 2 to about 6, about 2 to about 4, about 3 to about 10, about 3 to about 8, about 3 to about 6, about 3 to about 5, about 3 to about 4, about 4 to about 6, about 4 to about 8, or about 4 to about 10, when measured with a 10 GHz signal.

[0106] Linear regression analysis and the genetic algorithm framework may not capture all compositions that can be used to form glasses according to the present disclosure, respectively. There may be some instances where linear regression analysis captures compositions that are contained within the convex hull of Table 4 and / or Table 5 and have desirable dielectric properties, but are not captured by the genetic algorithm framework, and vice versa. By evaluating compositions using both linear regression analysis and the genetic algorithm framework, the likelihood of failing to identify compositions that are within the space defined by the convex hull and have a dielectric constant of 10 or less when measured with a 10 GHz signal is reduced.

[0107] According to another aspect of the disclosure, an exemplary glass is defined by a convex hull of exemplary glass composition C of Table 4 and / or exemplary glass composition D of Table 5, and is represented by the following formulas 3 and 4 (in mole percent of oxides): 0.429780863-0.00424207*[SiO2]-0.004096119*[Al2O3]-0.004396116*[B 2O3]-0.002791817*[Li2O]-0.012890989*[K2O]-0.004226519*[MgO]-0.00 4108234*[CaO]-0.003587217*[SrO]-0.004083111*[BaO]-0.028056812*[S nO2]-0.004220402*[ZnO]+0.000195707*[La2O3]-0.004466313*[F]≦0.008 formula 3 and 0.00454540427936441+0.00452303537205577*[K2O]+0.00026538565533632*[B2O3]+2.211176044138×10 -5 *[Al2O3]*[BaO]+6.27439041968789×10 -6 *2[CaO]-0.000215116681577554*[F]-6.01991751010702×10 -6 *[SiO2]*[B2O3]≦0.008 Equation 4 The glass can be derived from a glass precursor composition that satisfies at least one of the following criteria:

[0108] Equations 3 and 4 were derived by analyzing the measured loss tangents at 10 GHz signals for several example glasses of the present disclosure. Equation 3 and / or Equation 4 can be used to predict which of the glass compositions defined by the convex hull of Tables 4 and / or 5 can be made into glasses having a loss tangent of 0.008 or less when measured at 10 GHz signals. The data was analyzed using linear regression or a genetic algorithm in a manner similar to that described above for Equations 1 and 2 to determine a model for the measured loss tangent of the glass, along with the concentration (in mole percent of oxide) of 15 predetermined oxides in the glass precursor composition from which the glass was derived. The 15 predetermined oxides were the same as those used to determine Equations 1 and 2.

[0109] A loss tangent model was developed using oxide concentration and loss tangent measurements for the examples shown in Table 3. The experimental data in Table 3 was divided into two groups of roughly equal size (a teacher group and a test group) in the same manner as described above for Equations 1 and 2. The teacher group was used to develop the model using linear regression or a genetic algorithm, and the test group was used to test the validity of the model. The coefficient of determination ("R") of a least squares regression analysis of the loss tangent measurements for certain exemplary glasses in the test group was calculated as 2 " ) and the predicted loss tangent for this particular exemplary glass, a model fit was determined.

[0110] Equation 3 was determined using a linear regression analysis of approximately half of the examples in Table 3 (the teacher group). Figure 6 is a plot of the predicted loss tangent for the remaining examples (the test group) based on Equation 3 compared to the measured loss tangent for each example in the test group. The data points in Figure 6 correspond to the individual examples in Table 3, and the dotted lines represent a least-squares regression fit to the data points. The R of Equation 3 2 The value was 0.9436, indicating a good fit between the predicted and measured loss tangents for the test set examples.

[0111] Equation 4 was determined using a genetic algorithm framework and had an R of at least 0.9. 2A nonlinear random function was evolved for many generations, with hundreds of iterations in each generation, until multiple functions with values ​​were found. Equation 4 shows that R 2 was selected from the list of generated functions based on the value and the number of fitting parameters of the generated function (i.e., R 2 (The R value is an indication of the accuracy of the function; the simpler the function, the smaller the fitting parameters.) Figure 7 is a plot of the predicted loss tangent for the remaining examples (the test set) based on Equation 4 compared to the measured loss tangent for each example in the test set. The data points in Figure 7 correspond to the individual examples in Table 3, and the dotted lines represent the least squares regression fit to the data points. The R value of Equation 4 2 The value was 0.9136, which indicates a good fit between the predicted and measured dielectric constants for glass.

[0112] To determine whether the test glass composition satisfies Equation 3 and / or Equation 4, the above equations are solved using the corresponding oxide concentrations in the glass composition. If the solved equations output a value less than or equal to 0.008, the test glass composition satisfies the above equations. If the solved equations output a value greater than 0.008, the test glass composition does not satisfy the above equations. With respect to Equations 3 and 4, the good fit between the predicted and measured dielectric constants for the test set of examples indicates at least a reasonable expectation to use Equation 3 and / or 4 to predict whether a composition will have a loss tangent less than or equal to 0.008 when measured at 10 GHz.

[0113] If a glass composition is defined by the convex hull of Table 4 and / or Table 5 and does not satisfy either Equation 3 or Equation 4, then a glass derived from this particular composition is unlikely to exhibit a loss tangent of 0.008 or less when measured with a 10 GHz signal. If a glass composition is defined by the convex hull of Table 4 and / or Table 5 and satisfies both Equation 3 and Equation 4, then such a glass is likely to have a loss tangent of 0.008 or less when measured with a 10 GHz signal, and thus falls within the scope of the exemplary glasses of the present disclosure. If a glass composition is defined by the convex hull of Table 4 and / or Table 5 and satisfies only one of Equation 3 and Equation 4, then such a glass is likely to have a loss tangent of 0.008 or less when measured with a 10 GHz signal, and thus falls within the scope of the exemplary glasses of the present disclosure. Glasses derived from precursor compositions satisfying Equation 3 and / or Equation 4 can have a measured loss tangent of about 0.008 or less, about 0.005 or less, about 0.0025 or less, or about 0.001 or less, when measured with a 10 GHz signal. In some embodiments, glasses derived from precursor compositions satisfying Equation 3 and / or Equation 4 can have a measured loss tangent of from about 0.0004 to about 0.01, from about 0.001 to about 0.01, from about 0.0025 to about 0.01, from about 0.005 to about 0.01, from about 0.0004 to about 0.001, from about 0.0004 to about 0.0025, from about 0.0004 to about 0.005, from about 0.001 to about 0.0025, from about 0.001 to about 0.005, from about 0.0025 to about 0.005, from about 0.0004 to about 0.008, from about 0.001 to about 0.008, from about 0.0025 to about 0.008, or from about 0.005 to about 0.008 when measured with a 10 GHz signal.

[0114] Linear regression analysis and the genetic algorithm framework may not capture all compositions that can be used to form glasses according to the present disclosure, respectively. There may be some instances where linear regression analysis captures compositions that are encompassed by the convex hull of Table 4 and / or Table 5 and have desirable dielectric properties, but are not captured by the genetic algorithm framework, and vice versa. By evaluating compositions using both linear regression analysis and the genetic algorithm framework, the likelihood of failing to identify compositions that are within the space defined by the convex hull and have a loss tangent of 0.008 or less when measured with a 10 GHz signal is reduced.

[0115] In some embodiments of the present disclosure, a glass according to the present disclosure is a glass that: (a) is contained within a convex hull defined by the boundary points of Table 4 and / or Table 5; (b) satisfies Equation 1 and / or Equation 2; and (c) satisfies Equation 3 and / or 4. Glass satisfying all three elements (a), (b), and (c) has a relative dielectric constant of about 10 or less, about 7.5 or less, about 5 or less, about 4 or less, about 3 or less, about 2 to about 10, about 3 to about 10, about 4 to about 10, about 5 to about 10, about 6 to about 10, about 7 to about 10, about 8 to about 10, about 9 to about 10, about 2 to about 8, about 2 to about 6, about 2 to about 4, about 3 to about 10, about 3 to about 8, about 3 to about 6, about 3 to about 5, about 3 to about 4, about 4 to about 6, about 4 to about 8, or about 4 to about 10, when measured with a 10 GHz signal. It may be combined with a loss tangent of about 0.001 or less, about 0.0004 to about 0.01, about 0.001 to about 0.01, about 0.0025 to about 0.01, about 0.005 to about 0.01, about 0.0004 to about 0.001, about 0.0004 to about 0.0025, about 0.0004 to about 0.005, about 0.001 to about 0.0025, about 0.001 to about 0.005, about 0.0025 to about 0.005, about 0.0004 to about 0.008, about 0.001 to about 0.008, about 0.0025 to about 0.008, or about 0.005 to about 0.008. EXAMPLES

[0116] The following examples illustrate various features and advantages provided by the present disclosure and are not intended to limit the scope of the invention and the appended claims in any way.

[0117] Example 1 Table 6 below lists exemplary glasses ("EG") according to the present disclosure in mole % calculated on an oxide basis from the as-batched glasses (glass precursor compositions from which the glasses are derived). Glass samples were prepared by mixing powder batches in a turbula for 60 minutes and melting at 1650°C in jacketed platinum crucibles for 16 hours. The molten glass was poured out as a block and annealed at 550-600°C. Glass properties were measured by standard methods or predictive models.

[0118] For the data presented in Table 6, the CTE was determined by fiber elongation techniques or predicted over the temperature range of 0°C to 300°C (±5°C) and is expressed as "x10 -7 The softening point ("Soft Pt."), annealing point ("Ann. Pt."), and strain point ("Str. Pt.") are expressed in °C. The elastic modulus ("E-mod"), also known as Young's modulus, is expressed in gigapascals (GPa), and density is expressed in g / cm. 3 viscosity is expressed in units of poise.

[0119] The 200 poise melting point (defined as the temperature at which the glass melt exhibits a viscosity of 200 poise) is expressed in °C. The 200 poise melting point was calculated using a fit of the Vogel-Fulcher-Tammann equation to high temperature viscosity data (measured by rotating cylinder viscometry per ASTM C965-81). The liquidus temperature of the glass was measured using a standard liquidus method which involves placing crushed glass particles in a platinum boat, placing the boat in a furnace with a gradient temperature zone, heating the boat at the appropriate temperature zone for 24 hours, and determining by microscopic examination the highest temperature at which crystals appear within the glass. The liquidus viscosity (in poise) is determined by this temperature and the coefficients (A, B, and T) of the Vogel-Fulcher-Tammann equation. o ) was determined.

[0120] The dielectric properties were measured on polished, as-prepared glass samples measuring 3 in. x 3 in. (7.62 cm x 7.62 cm) and less than 1 mm thick. The test frequencies ranged from 2.7 GHz to 50 GHz. The dielectric constant D k The dielectric constant and loss tangent were determined for each sample. The samples were tested using a split post dielectric resonator at signal frequencies below 10 GHz, or using an open cavity resonator at signal frequencies above 10 GHz. In each case, the dielectric constant and loss tangent were measured from the shift and broadening of the resonance peak.

[0121] [Table 6]

[0122] EG1 illustrates glasses that are alkali metal-free and have increased amounts of B2O3, which may be desirable in some applications. EG2 demonstrates the effect of replacing a portion of SiO2 and B2O3 with Al2O3 on the viscosity of the glass. Samples EG1-EG6 also demonstrate the effect that RO, Al2O3, and B2O3 content can have on the melting and forming properties of the glass. Without being bound by any particular theory, it has been found that the melting and forming properties of the exemplary glasses EG1-EG6 are improved relative to the other glasses when the RO, Al2O3, and B2O3 content of the glass is adjusted to meet a ratio of RO:(Al2O3+(0.5*B2O3)) of about 0 to about 0.5.

[0123] The data in Table 6 further demonstrates that the exemplary glasses have a low dielectric constant D k and loss tangent. Without being bound by any particular theory, it has been found that the dielectric properties are improved when SiO2, B2O3, and Al2O3 are present in amounts that satisfy a ratio B2O3:(Al2O3+SiO2) of about 0.22 to about 0.35. Thus, the data in Table 6 demonstrates that the glasses of the present disclosure can exhibit improved dielectric properties in combination with improved formability.

[0124] Exemplary glasses EG2-EG5 show that glasses according to the present disclosure feature low loss tangents of about 0.001 or less at signal frequencies of 10 GHz. As discussed above, low loss tangents at 10 GHz are important in supporting the expected increase in data rates at frequencies above 10 GHz. Additionally, exemplary glasses of the present disclosure also exhibit low dielectric constants (less than 5). Materials with high dielectric constants are generally not suitable for the continued scaling of microelectronic devices, as signal reflections can be affected by the dielectric constant. Thus, low dielectric constants such as those exhibited by exemplary glasses herein may be suitable for use in smaller, scaled devices.

[0125] Figure 1 is a chart comparing the dielectric constant and loss tangent at a signal frequency of 10 GHz for exemplary glasses EG2, EG3, and EG4, water, sapphire, Teflon, silicon, and soda lime. As demonstrated in Figure 1, the exemplary glasses of the present disclosure provide a good balance of low dielectric constant and low loss tangent. Thus, the glasses of the present disclosure provide an additional alternative material for use in applications where low dielectric constant and low loss tangent are required.

[0126] The data in Table 6 also demonstrate that the exemplary glasses EG1-EG6 exhibit relatively low CTE values. Thus, these exemplary glasses exhibit improved dielectric properties and formability while maintaining relatively low CTE values. As discussed above, low CTE values ​​can be useful in forming glass laminates that include a core and one or more cladding layers.

[0127] The exemplary glasses EG1-EG4 all have predicted softening points above 700° C., which is much higher than the solder reflow temperatures typically seen in PCB processing (usually 260° C. for 30 seconds). The data in Table 6 indicates that the glasses of the present disclosure are likely to be characterized by dimensional stability for 30 seconds when heated to 260° C. As discussed above, such dimensional stability characteristics, combined with the dielectric properties of the exemplary glasses and their formability, indicate that the glasses of the present disclosure may be suitable for use as insulation layer laminates in PCB applications.

[0128] Example 2 Tables 7-9 show the dielectric properties of exemplary glasses EG2-EG4 over the signal frequency range of about 9.6 GHz to about 21 GHz. The dielectric constant and loss tangent data were obtained in the same manner as described above with respect to Example 1. The data in Tables 7-9 show that the glasses of the present disclosure can maintain low dielectric constants and low loss tangents at signal frequencies above 10 GHz.

[0129] [Table 7]

[0130] [Table 8]

[0131] [Table 9]

[0132] Example 3 Table 10 shows the dielectric properties of the exemplary glass EG5 over the signal frequency range of about 2.6 GHz to about 9.9 GHz. The dielectric constant and loss tangent data were obtained in the same manner as described above with respect to Example 1. Table 10 shows that EG5 exhibits a low dielectric constant and extremely low loss tangent at signal frequencies up to at least about 10 GHz.

[0133] [Table 10]

[0134] Example 4 Table 3 lists the measured dielectric constant and loss tangent for exemplary glasses according to the present disclosure ("EG") in mole percent calculated on an oxide basis from the glass precursor composition (as-batched composition). Glass samples were prepared by mixing the powder batch in a turbula for 60 minutes and melting at 1650°C for 16 hours in a coated platinum crucible. The molten glass was poured out as a block and annealed at 550-600°C. Dielectric properties were measured on polished, as-prepared glass samples measuring 3 inches by 3 inches (7.62 cm by 7.62 cm) and less than 1 mm thick. Test frequencies range from 2.7 GHz to 50 GHz. Dielectric constant D k The dielectric constant and loss tangent were determined for each sample. The samples were tested using a split post dielectric resonator at signal frequencies below 10 GHz, or using an open cavity resonator at signal frequencies above 10 GHz. In each case, the dielectric constant and loss tangent were measured from the shift and broadening of the resonance peak.

[0135] Example 5 Tables 11 and 12 show exemplary glasses EG39-EG57 according to the present disclosure in mole percent calculated on an oxide basis from the as-batched glasses (the glass precursor compositions from which the glasses are derived). The glass samples were prepared and characterized as described above for the exemplary glasses of Example 1.

[0136] To demonstrate the effect of RO concentration and content on the dielectric properties of the glasses, such as dielectric constant and loss tangent, the glass compositions used to form the exemplary glasses EG39-EG57 all contained the same amount of SiO2 and similar ratios of B2O3:Al2O3. Table 11 includes exemplary glasses EG39-EG50, which contain a single RO species as shown in Table 11. Table 12 includes exemplary glasses EG51-57, which contain a combination of two RO species as shown in Table 12. The dielectric constants D reported in Tables 11 and 12 are k and loss tangent values ​​were measured at a signal frequency of 10 GHz.

[0137] [Table 11-1]

[0138] [Table 11-2]

[0139] [Table 12-1]

[0140] [Table 12-2]

[0141] Figures 8A and 8B show the relative permittivity and loss tangent, respectively, measured with a 10 GHz signal as a function of RO concentration for a single RO species. Figures 8A and 8B plot the relative permittivity and loss tangent, respectively, for examples having a single RO species at concentrations of approximately 2.1 mol%, 5.1 mol%, and 8.1 mol%: MgO (EG39 - EG41), CaO (EG42 - EG44), SrO (EG45 - EG47), and BaO (EG48 - EG50). The plot in Figure 8A demonstrates that the relative permittivity increases with increasing RO content. Also, the data in Figure 8A demonstrate that at a given RO species concentration, the relative permittivity increases based on the RO species in the order Mg < Ca < Sr < Ba. This relationship suggests that the relative permittivity may increase with a decrease in the size of the cation and may also increase with an increase in the cation field strength. Also, the data in Figure 8A show that the relative permittivity as a function of SrO concentration is similar to the relative permittivity as a function of CaO concentration, suggesting that both CaO and SrO are potential candidates for mixing with MgO to provide a glass with the desired dielectric properties.

[0142] The plot in Figure 8B demonstrates that the loss tangent increases with increasing RO content. Also, the data in Figure 8B demonstrate that at a given RO species concentration, the loss tangent increases based on the RO species in the order Mg < Ca < Sr < Ba at approximately 5.1 mol%, but at approximately 2.1 mol% and approximately 8.1 mol%, SrO-containing glasses have a loss tangent generally equal to or less than that of the corresponding concentration of CaO-containing glass samples. The data in Figure 8B demonstrate the similarity between the loss tangent as a function of SrO concentration and the loss tangent as a function of CaO concentration, which may indicate that both CaO and SrO are potential candidates for mixing with MgO to provide a glass with the desired dielectric properties.

[0143] The data presented in Figures 8A and 8B show that reducing the concentration of RO species in the glass compositions of the present disclosure can result in a decrease in the dielectric constant and loss tangent of the glass when only a single type of RO species is present.

[0144] 9A and 9B compare the dielectric constant and loss tangent, respectively, of glasses containing a single RO species or a mixture of RO species. The X-axis of both plots is the total amount of RO present in the glass composition (RO Total The data in FIG. 9A shows the ratio of RO species (MgO, CaO, or BaO) to RO species (MgO, CaO, or BaO) for the single RO species example and the mixed RO species example. Total Figure 8A shows that examples with mixed RO species such as MgO+CaO (EG55-57) and MgO+SrO (EG61) exhibit lower dielectric constants than examples with a single type of RO species, even when the dielectric constants are roughly the same. For example, EG55-57, which contains both MgO and CaO, exhibit lower dielectric constants than the corresponding single RO species example glasses EG41 (MgO) and EG44 (CaO). Combinations of CaO or SrO with BaO (EG58 and EG59, respectively) result in glasses with lower dielectric constants than BaO alone (EG50). EG61 demonstrates that by combining MgO with SrO, it is possible to produce glasses with lower dielectric constants than SrO alone (EG47). Figure 8A shows that for a single RO species, the dielectric constant decreased with decreasing RO content. The data shown in Figure 9A indicates that in applications where a relatively large amount of total RO is desired, combining two or more RO species can improve the dielectric constant of a given RO. Total It has been demonstrated that the glasses of the present disclosure can provide a lower dielectric constant for glasses having a single RO species relative to glasses having a single RO species. For example, increasing the concentration of RO in the glass composition can help lower the liquidus temperature, but as shown in Figure 8A, when only a single RO species is used, increasing the concentration of RO increases the dielectric constant of the glass. Mixing RO species, such as MgO+CaO or MgO+SrO, can help provide the desired reduction in liquidus temperature while also reducing the dielectric constant of the glass.

[0145] The data in FIG. 9B shows the RO concentration for the single RO species example and the mixed RO species example. Total EG55-57, which contains both MgO and CaO, show a lower loss tangent than the examples with only CaO, SrO, or BaO as RO species, even when the loss tangents are roughly the same. For example, EG55-57, which contains both MgO and CaO, show a lower loss tangent than the examples with only CaO, SrO, or BaO as RO species. Combinations of CaO or SrO with BaO (EG58 and EG59, respectively) result in glasses with lower loss tangents than BaO alone (EG50). EG61 demonstrates that by combining MgO with SrO, it is possible to produce glasses with lower loss tangents than SrO alone (EG47). FIG. 8B shows that for the single RO species, the loss tangent decreased with decreasing RO content. The data presented in FIG. 9B indicates that in applications where a relatively large amount of total RO is desired, combining two or more RO species can reduce the overall yield of a given RO. Total 9B demonstrates that the presently disclosed glasses can provide a lower loss tangent for glasses having only CaO, SrO, or BaO as a single RO species. The lowest loss tangent was observed for the example (EG41) containing only MgO as the single RO species. However, the data in FIG. 9B indicates that in applications where the presence of RO species other than MgO, such as CaO, SrO, or BaO, is desired, combining these species with MgO will likely result in a glass with a lower loss tangent than a comparable glass containing only CaO, SrO, or BaO as a single RO species.

[0146] 10A and 10B show the dielectric constant and loss tangent of the single and mixed RO species examples from Tables 11 and 12, respectively, as a function of glass density. R 2 The data in Figures 10A and 10B show an R value of about 0.95 or greater. 2 The values ​​suggest a linear relationship between the density of the exemplary glasses with mixed RO species with respect to the dielectric constant and loss tangent, respectively.

[0147] Without wishing to be bound by any theory, it is believed that the effect of RO concentration and type in the mixed RO species may be related to the molar volume and molecular polarizability of the glass. FIG. 11 compares the measured dielectric constant for several examples of single and mixed RO species exemplary glasses from Tables 11 and 12 with the dielectric constant predicted using the Clausius-Mossotti equation and additivity rule. The dielectric constant (D k ) is expressed by the Clausius-Mossotti equation (Equation 5):

[0148]

number

[0149] can be predicted using

[0150] V m is the molar volume of the glass, and α D is the molecular polarizability of the glass. R of least squares regression for exemplary glasses with single and mixed RO species 2 The values ​​are also shown. R for the mixed RO species example 2 The values ​​are greater than 0.97, indicating that the Clausius-Mossotti equation and additivity rules can be used to predict with reasonable accuracy the dielectric constants of the exemplary glasses in Table 12. This suggests that the effect of mixed RO species on the dielectric constant of the glass may be related, at least in part, to the molar volume and molecular polarizability of the glass.

[0151] Example 6 Table 13 lists exemplary glasses EG62-EG76 according to the present disclosure in mole percent calculated on an oxide basis from the as-batched glasses (the glass precursor compositions from which the glasses are derived). The glass samples were prepared and characterized as described above for the exemplary glasses of Example 1.

[0152] [Table 13-1]

[0153] [Table 13-2]

[0154] [Table 13-3]

[0155] The following non-limiting aspects are included in the present disclosure.

[0156] According to a first aspect of the present disclosure, an article comprises a glass comprising about 60% to about 80% SiO, 0% to about 13% AlO, about 15% to about 28% BO, 0% to about 1% of at least one fining agent, and 0% to about 15% total (in mole percent of oxide) of one or more alkaline earth oxides (RO), where RO is selected from CaO, MgO, BaO, and SrO, and the ratio of BO:(AlO+SiO) is about 0.13 to about 0.35, and the glass has a dielectric constant of about 10 or less and a loss tangent of about 0.01 or less, all measured with a 10 GHz signal.

[0157] A second aspect of the present disclosure relates to the article of aspect 1, wherein the fining agent comprises one or more of SnO2, Sb2O3, As2O3, and a halogen salt.

[0158] A third aspect of the present disclosure relates to the article of aspect 1, wherein the glass further comprises (by oxide mole percent) about 2% to about 15% combined of one or more of CaO, MgO, BaO, and SrO.

[0159] A fourth aspect of the present disclosure relates to the article of aspect 3, wherein the glass further comprises (in oxide mole percent) about 1% to about 13% MgO and about 0.1% to about 10% CaO.

[0160] A fifth aspect of the present disclosure relates to the article of aspect 1, wherein the glass comprises greater than 0 mol % and less than or equal to 8.5 mol % RO and further has a dielectric constant less than or equal to about 6 and / or a loss tangent less than or equal to about 0.004, both measured with a 10 GHz signal.

[0161] A sixth aspect of the present disclosure relates to the article of aspect 1, wherein the ratio of B2O3:(Al2O3+SiO2) is from about 0.22 to about 0.35.

[0162] A seventh aspect of the present disclosure relates to the article of aspect 1, wherein the ratio of RO:(Al2O3+(0.5*B2O3)) is from 0 to about 0.9.

[0163] An eighth aspect of the present disclosure relates to the article of aspect 1, wherein the ratio of RO:(Al2O3+(0.5*B2O3)) is from about 0.2 to about 0.9.

[0164] A ninth aspect of the present disclosure relates to the article of aspect 1, wherein the glass further comprises (in mole percent of oxides): about 64% to about 75% SiO; about 1% to about 12% AlO; and about 16% to about 26% BO.

[0165] A tenth aspect of the present disclosure relates to the article of any one of the first to ninth aspects, wherein the glass has a dielectric constant of about 7.5 or less and a loss tangent of about 0.005 or less, as measured with a 10 GHz signal.

[0166] An eleventh aspect of the present disclosure relates to the article of any one of the first to ninth aspects, wherein the glass has a dielectric constant of about 5 or less and a loss tangent of about 0.005 or less, as measured with a 10 GHz signal.

[0167] A twelfth aspect of the present disclosure relates to the article of any one of the first to eleventh aspects, wherein the glass comprises no more than trace amounts of alkali metal oxides.

[0168] In a thirteenth aspect of the present disclosure, the glass has a viscosity of about 25×10 when measured at 0° C. to 300° C. -7 / ℃ ~ approx. 65×10 -7 13. The article of any one of embodiments 1-12, having an average coefficient of thermal expansion (CTE) of 1 / °C.

[0169] A fourteenth aspect of the present disclosure relates to the article of any one of the first to thirteenth aspects, wherein the glass has dimensional stability at 260° C. for 30 seconds.

[0170] According to a fifteenth aspect of the present disclosure, an article includes a glass comprising about 60% to about 80% SiO, 0% to about 13% Al2O3, about 15% to about 28% B2O3, 0% to about 1% of at least one fining agent, and 0% to about 15% total (in mole percent of oxides) of one or more alkaline earth oxides (RO), where RO is selected from CaO, MgO, BaO, and SrO, and the ratio of RO:(Al2O3+(0.5*B2O3)) is about 0 to about 0.9, and the glass has a liquidus viscosity of about 40 kpoise to about 5000 kpoise.

[0171] A sixteenth aspect of the present disclosure relates to the article of the fifteenth aspect, wherein the fining agent comprises one or more of SnO2, Sb2O3, As2O3, and a halogen salt.

[0172] A seventeenth aspect of the present disclosure relates to the article of aspect 16, wherein the glass further comprises one or more of CaO, MgO, BaO, and SrO in a total amount between about 2% and about 15% (by oxide mole percent).

[0173] An eighteenth aspect of the present disclosure relates to the article of aspect 17, wherein the glass further comprises (in oxide mole percent) about 1% to about 13% MgO and about 0.1% to about 10% CaO.

[0174] A nineteenth aspect of the present disclosure relates to the article of aspect 15, wherein the glass comprises greater than 0 mol % and less than or equal to 8.5 mol % RO, and further has a dielectric constant less than or equal to about 6 and / or a loss tangent less than or equal to about 0.004, both measured with a 10 GHz signal.

[0175] A twentieth aspect of the present disclosure relates to the article of the fifteenth aspect, wherein the ratio of RO:(Al2O3+(0.5*B2O3)) is from about 0.2 to about 0.9.

[0176] A twenty-first embodiment of the present disclosure relates to the article of embodiment 15, wherein the ratio of B2O3:(Al2O3+SiO2) is from about 0.13 to about 0.35.

[0177] A twenty-second embodiment of the present disclosure relates to the article of embodiment 21, wherein the ratio of B2O3:(Al2O3+SiO2) is from about 0.22 to about 0.35.

[0178] A twenty-third embodiment of the present disclosure relates to the article of embodiment 15, wherein the glass further comprises (in mole percent of oxides): about 65% to about 80% SiO; about 1% to about 8% AlO; and about 16% to about 26% BO.

[0179] A twenty-fourth aspect of the present disclosure relates to the article of any one of aspects fifteen to twenty-third, wherein the glass further has a 35,000 poise temperature of from about 1110°C to about 1325°C.

[0180] A twenty-fifth aspect of the present disclosure relates to the article of any one of aspects fifteen to twenty-four, wherein the glass further has a 200 poise melting point of about 1600°C to about 1825°C.

[0181] A twenty-sixth aspect of the present disclosure relates to the article of any one of aspects fifteen to twenty-fifth, wherein the glass comprises no more than trace amounts of alkali metal oxides.

[0182] In a twenty-seventh aspect of the present disclosure, the glass has a viscosity of about 25×10 when measured at 0° C. to 300° C. -7 / ℃ ~ approx. 65×10 -7 27. The article of any one of embodiments 15-26, having an average coefficient of thermal expansion (CTE) of 1 / °C.

[0183] A twenty-eighth embodiment of the present disclosure relates to the article of any one of embodiments fifteen to twenty-seven, wherein the glass further has a liquidus viscosity of from about 50 kpoise to about 3000 kpoise.

[0184] A twenty-ninth aspect of the present disclosure relates to the article of any one of aspects fifteen to twenty-eight, wherein the glass has dimensional stability at 260° C. for 30 seconds.

[0185] According to a thirtieth aspect of the present disclosure, an article comprises a glass comprising about 60% to about 80% SiO, 0% to about 13% AlO, about 15% to about 28% BO, 0% to about 1% of at least one fining agent, and 0% to about 15% total (in mole percent of oxide) of one or more alkaline earth oxides (RO), where RO is selected from CaO, MgO, BaO, and SrO, and the ratio of BO:(AlO+SiO) is about 0.13 to about 0.35, the glass having a dielectric constant of about 10 or less and a loss tangent of about 0.01 or less as measured with a 10 GHz signal, and further the glass having a liquidus viscosity of about 40 kpoise to about 5000 kpoise.

[0186] A thirty-first aspect of the present disclosure relates to the article of the thirty-first aspect, wherein the fining agent comprises one or more of SnO 2 , Sb 2 O 3 , As 2 O 3 , and a halogen salt.

[0187] A thirty-second aspect of the present disclosure relates to the article of aspect 30, wherein the glass has a dielectric constant of about 7.5 or less and a loss tangent of about 0.005 or less, as measured with a 10 GHz signal.

[0188] A thirty-third aspect of the present disclosure relates to the article of the thirty-first aspect, wherein the glass has a dielectric constant of about 5 or less and a loss tangent of about 0.005 or less, as measured with a 10 GHz signal.

[0189] A thirty-fourth aspect of the present disclosure relates to the article of any one of aspects thirty to thirty-three, wherein the glass has a liquidus viscosity of about 50 kpoise to about 3000 kpoise.

[0190] A thirty-fifth embodiment of the present disclosure relates to the article of any one of embodiments thirty to thirty-four, wherein the glass further has a 35,000 poise temperature of from about 1110°C to about 1325°C.

[0191] A thirty-sixth aspect of the present disclosure relates to the article of any one of aspects 30 to 35, wherein the glass further comprises (in mole percent of oxides): about 64% to about 75% SiO; about 1% to about 12% AlO; and about 16% to about 26% BO.

[0192] A thirty-seventh embodiment of the present disclosure relates to the article of the thirty-first embodiment, wherein the ratio of B2O3:(Al2O3+SiO2) is from about 0.22 to about 0.35.

[0193] A thirty-eighth embodiment of the present disclosure relates to the article of embodiment 30, wherein the ratio of RO:(Al2O3+(0.5*B2O3)) is from about 0 to about 0.9.

[0194] A thirty-ninth embodiment of the present disclosure relates to the article of the thirty-eighth embodiment, wherein the ratio of RO:(Al2O3+(0.5*B2O3)) is from about 0.2 to about 0.9.

[0195] According to a fortieth aspect of the present disclosure, an article includes a glass comprising about 60% to about 80% SiO2, 0% to about 13% Al2O3, about 15% to about 28% B2O3, 0% to about 1% of at least one fining agent, and MgO and at least one additional alkaline earth oxide (RO), where the at least one additional RO is selected from CaO, BaO, and SrO, and the total amount of MgO and the at least one additional RO combined (RO Total ) is from about 3% to about 15% (in terms of oxide mole percent), and the glasses have a dielectric constant of about 10 or less and / or a loss tangent of about 0.01 or less, all measured with a 10 GHz signal.

[0196] A forty-first aspect of the present disclosure relates to the article of aspect 40, further having a loss tangent of less than or equal to about 0.008 as measured with a 10 GHz signal.

[0197] A forty-second aspect of the present disclosure relates to the article of aspect 40, wherein the glass has a dielectric constant of about 7.5 or less and a loss tangent of about 0.005 or less, both measured with a 10 GHz signal.

[0198] A forty-third aspect of the present disclosure is a MgO:RO Total A ratio of at least 0.3.

[0199] A forty-fourth aspect of the present disclosure is a MgO:RO Total A ratio of at least 0.5.

[0200] A forty-fifth aspect of the present disclosure is a method for producing a RO Total is about 4% to about 15 mol % (in terms of oxide mole percent).

[0201] A forty-sixth aspect of the present disclosure is a method for producing a RO Total 46. ​​The article of any one of embodiments 40-45, wherein the ratio of Al2O3 to Pb2O3 is greater than 1.

[0202] A forty-seventh embodiment of the present disclosure relates to the article of any one of embodiments 40 to 46, wherein the ratio of B2O3:(Al2O3+SiO2) is from about 0.13 to about 0.35.

[0203] A forty-eighth embodiment of the present disclosure relates to the article of any one of embodiments 40 to 47, wherein the at least one additional RO is CaO, and further wherein (in terms of oxide mole percent) MgO is present in an amount between about 1% and about 10%, and CaO is present in an amount between about 1% and about 10%.

[0204] A forty-ninth aspect of the present disclosure relates to the article of any one of aspects 40 to 47, wherein the at least one additional RO is CaO, and further wherein (in terms of oxide mole percent) MgO is present in an amount between about 1% and about 7%, and CaO is present in an amount between about 2% and about 7%.

[0205] A 50th aspect of the present disclosure relates to the article of any one of aspects 40 to 47, wherein the at least one additional RO is SrO, and further wherein (in mole percent of oxides) MgO is present in an amount between about 1% and about 10%, and SrO is present in an amount between about 1% and about 5%.

[0206] A fifty-first aspect of the present disclosure relates to the article of any one of aspects 40 to 50, wherein the fining agent comprises one or more of SnO2, Sb2O3, As2O3, and a halogen salt.

[0207] A fifty-second aspect of the present disclosure is a RO Total 52. The article of any one of aspects 40 to 51, wherein the ratio of (Al2O3+B2O3) is from about 0.2 to about 0.6.

[0208] A fifty-third aspect of the present disclosure relates to the article of any one of aspects forty to fifty-second, wherein the glass is substantially free of alkali metal oxides.

[0209] A fifty-fourth aspect of the present disclosure relates to the article of any one of aspects forty to fifty-three, wherein the glass has a density of about 2.2 to about 2.5 grams per cubic centimeter when measured at about 25°C.

[0210] A fifty-fifth embodiment of the present disclosure relates to the article of any one of embodiments forty to fifty-four, wherein the glass further has a 35,000 poise temperature of from about 1110°C to about 1325°C.

[0211] A fifty-sixth embodiment of the present disclosure relates to the article of any one of embodiments forty to fifty-fifty-fifty, wherein the glass further has a 200 poise melting point of about 1600°C to about 1825°C.

[0212] According to a fifty-seventh aspect of the present disclosure, an article for a substrate of an electronic device includes a glass consisting essentially of about 60% to about 80% SiO2, 0% to about 13% Al2O3, about 15% to about 28% B2O3, 0% to about 1% of at least one fining agent, and MgO and at least one additional alkaline earth oxide (RO), where the at least one additional RO is selected from CaO, BaO, and SrO, and the total amount of MgO and the at least one additional RO combined (RO Total ) is from about 3% to about 15% (in terms of oxide mole percent), and the glasses have a dielectric constant of about 10 or less and / or a loss tangent of about 0.01 or less, all measured with a 10 GHz signal.

[0213] A fifty-eighth aspect of the present disclosure relates to the article of aspect fifty-seven, further having a loss tangent of less than or equal to about 0.008 as measured with a 10 GHz signal.

[0214] A fifty-ninth aspect of the present disclosure relates to the article of aspect fifty-seven, wherein the glass has a dielectric constant of about 7.5 or less and a loss tangent of about 0.005 or less, both measured with a 10 GHz signal.

[0215] A sixtieth aspect of the present disclosure is a MgO:RO Total The article of any one of embodiments 57-59, wherein the ratio is at least 0.3.

[0216] A sixty-first aspect of the present disclosure is a MgO:RO Total The article of any one of embodiments 57-59, wherein the ratio is at least 0.5.

[0217] A sixty-second aspect of the present disclosure is a method for producing a RO Total is about 4% to about 15 mol % (in terms of oxide mole percent).

[0218] A sixty-third aspect of the present disclosure is a method for producing a RO Total 63. The article of any one of embodiments 57-62, wherein the ratio of Al2O3 to Pb2O3 is greater than 1.

[0219] A sixty-fourth embodiment of the present disclosure relates to the article of any one of embodiments 57 to 63, wherein the ratio of B2O3:(Al2O3+SiO2) is from about 0.13 to about 0.35.

[0220] A sixty-fifth embodiment of the present disclosure relates to the article of any one of embodiments 57 to 64, wherein the at least one additional RO is CaO, and further wherein (in terms of oxide mole percent) MgO is present in an amount between about 1% and about 10%, and CaO is present in an amount between about 1% and about 10%.

[0221] A sixty-sixth embodiment of the present disclosure relates to the article of any one of embodiments 57 to 64, wherein the at least one additional RO is CaO, and further wherein (in terms of oxide mole percent) MgO is present in an amount between about 1% and about 7%, and CaO is present in an amount between about 2% and about 7%.

[0222] A sixty-seventh embodiment of the present disclosure relates to the article of any one of embodiments 57 to 64, wherein the at least one additional RO is SrO, and further wherein (in mole percent of oxides) MgO is present in an amount between about 1% and about 10%, and SrO is present in an amount between about 1% and about 5%.

[0223] A sixty-eighth aspect of the present disclosure relates to the article of any one of aspects 57 to 67, wherein the fining agent comprises one or more of SnO2, Sb2O3, As2O3, and a halogen salt.

[0224] A sixty-ninth aspect of the present disclosure is a method for producing a RO Total 69. The article of any one of aspects 57-68, wherein the ratio of (Al2O3+B2O3) is from about 0.2 to about 0.6.

[0225] A seventieth aspect of the present disclosure relates to the article of any one of aspects 57 to 69, wherein the glass is substantially free of alkali metal oxides.

[0226] A seventy-first embodiment of the present disclosure relates to the article of any one of embodiments 57 to 70, wherein the glass has a density of about 2.2 to about 2.5 grams per cubic centimeter when measured at about 25° C.

[0227] A seventy-second embodiment of the present disclosure relates to the article of any one of embodiments 57 to 71, wherein the glass further has a 35,000 poise temperature of from about 1110°C to about 1325°C.

[0228] A seventy-third embodiment of the present disclosure relates to the article of any one of embodiments fifty-seven to seventy-second, wherein the glass further has a 200 poise melting point of about 1600°C to about 1825°C.

[0229] According to a seventy-fourth aspect of the present disclosure, an article includes a glass including SiO2, Al2O3, and B2O3, and at least one of Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, SnO2, ZnO, La2O3, F, and Fe2O3, where a first sum (X sum ), the second sum of Li2O, Na2O, K2O, MgO, CaO, SrO, and BaO (Y sum ), and the sum of SnO2, ZnO, La2O3, F, and Fe2O3 third (Z sum )(X sum , Y sum , and Z sum is the mole percent of oxide) at the boundary points: TIFF2025039835000023.tif45155

[0230] X as further defined by sum , Y sum , and Z sum is in the convex hull of The glass further comprises a compound represented by Formula 1 and Formula 2 (in mole percent of oxides): -42.8440902+0.463763055*[SiO2]+0.520077325*[Al2O3]+0.468168738 *[B2O3]+0.47253232*[Li2O]+2.11958583*[K2O]+0.499421381*[MgO]+0. 558094225*[CaO]+0.805792958*[SrO]+0.637349469*[BaO]-0.17232118* [SnO2]+0.525853343*[ZnO]+0.261394654*[La2O3]+0.469279089*[F]≦10 formula 1 and 0.756212572817506+[K2O]+0.209148876828416*[La2O3]+0.0884393206156657*[BaO]+0.0384462744417 211*[CaO]+(5.95212630529679-[F]) / [B2O3]+(254.196472343803-2.1615185467817*[B2O3]) / [SiO2]≦10 formula 2 is defined by at least one of Additionally, the glass has a dielectric constant of about 10 or less when measured with a 10 GHz signal.

[0231] A seventy-fifth aspect of the present disclosure is a glass having a loss tangent of about 0.008 or less as measured with a 10 GHz signal, and further comprising a glass having a composition satisfying Formula 3 and Formula 4 (in mole percent of oxides): 0.429780863-0.00424207*[SiO2]-0.004096119*[Al2O3]-0.004396116*[B 2O3]-0.002791817*[Li2O]-0.012890989*[K2O]-0.004226519*[MgO]-0.00 4108234*[CaO]-0.003587217*[SrO]-0.004083111*[BaO]-0.028056812*[S nO2]-0.004220402*[ZnO]+0.000195707*[La2O3]-0.004466313*[F]≦0.008 formula 3 and 0.00454540427936441+0.00452303537205577*[K2O]+0.00026538565533632*[B2O3]+2.211176044138×10 -5 *[Al2O3]*[BaO]+6.27439041968789×10 -6 *2[CaO]-0.000215116681577554*[F]-6.01991751010702×10 -6 *[SiO2]*[B2O3]≦0.008 Equation 4 The article of claim 74, wherein the article is defined by at least one of the following:

[0232] A seventy-sixth aspect of the present disclosure relates to the article of any one of aspects seventy-four or seventy-five, wherein the glass further has a dielectric constant of about 7.5 or less and a loss tangent of about 0.005 or less, as measured with a 10 GHz signal.

[0233] A seventy-seventh aspect of the present disclosure relates to the article of any one of aspects seventy-four or seventy-five, wherein the glass further has a dielectric constant of about 5 or less and a loss tangent of about 0.005 or less, as measured with a 10 GHz signal.

[0234] A seventy-eighth aspect of the present disclosure is a method for producing a glass comprising the steps of: providing a glass having a first total X, in mole percent of oxides, present in the glass; sum , the sum of the second Y sum , and the sum of the third Z sum is equal to 100.

[0235] A seventy-ninth aspect of the present disclosure relates to the article of any one of aspects 74 to 78, wherein the glass further comprises MgO and ZnO.

[0236] An eightieth aspect of the present disclosure relates to the article of any one of aspects 74 to 79, wherein the glass further comprises SnO2 and at least one of CaO and BaO.

[0237] An eighty-first aspect of the present disclosure relates to the article of any one of aspects 74 to 80, wherein the glass comprises no more than trace amounts of alkali metal oxides.

[0238] An eighty-second aspect of the present disclosure relates to the article of any one of aspects 74 to 81, wherein the glass is substantially free of at least one of F, La2O3, and ZnO.

[0239] An eighty-third aspect of the present disclosure relates to the article of any one of aspects seventy-four to eighty-first, wherein the glass further comprises at least one of F, La2O3, and ZnO.

[0240] According to an eighty-fourth aspect of the present disclosure, an article includes a glass including SiO2, Al2O3, and B2O3, and at least one of Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, SnO2, ZnO, La2O3, F, and Fe2O3, where a first sum (X sum ), the second sum of Li2O, Na2O, K2O, MgO, CaO, SrO, and BaO (Y sum ), and the sum of SnO2, ZnO, La2O3, F, and Fe2O3 third (Z sum )(X sum , Y sum , and Z sum is the mole percent of oxide) at the boundary points: TIFF2025039835000024.tif96157

[0241] X as further defined by sum , Y sum , and Z sum is in the convex hull of The glass further comprises a compound represented by Formula 1 and Formula 2 (in mole percent of oxides): -42.8440902+0.463763055*[SiO2]+0.520077325*[Al2O3]+0.468168738 *[B2O3]+0.47253232*[Li2O]+2.11958583*[K2O]+0.499421381*[MgO]+0. 558094225*[CaO]+0.805792958*[SrO]+0.637349469*[BaO]-0.17232118* [SnO2]+0.525853343*[ZnO]+0.261394654*[La2O3]+0.469279089*[F]≦10 formula 1 and 0.756212572817506+[K2O]+0.209148876828416*[La2O3]+0.0884393206156657*[BaO]+0.0384462744417 211*[CaO]+(5.95212630529679-[F]) / [B2O3]+(254.196472343803-2.1615185467817*[B2O3]) / [SiO2]≦10 formula 2 is defined by at least one of The glass further has a dielectric constant of about 10 or less when measured with a 10 GHz signal.

[0242] An eighty-fifth aspect of the present disclosure is a glass having a loss tangent of about 0.008 or less as measured with a 10 GHz signal, and further comprising a glass having a composition satisfying Formula 3 and Formula 4 (in mole percent of oxides): 0.429780863-0.00424207*[SiO2]-0.004096119*[Al2O3]-0.004396116*[B 2O3]-0.002791817*[Li2O]-0.012890989*[K2O]-0.004226519*[MgO]-0.00 4108234*[CaO]-0.003587217*[SrO]-0.004083111*[BaO]-0.028056812*[S nO2]-0.004220402*[ZnO]+0.000195707*[La2O3]-0.004466313*[F]≦0.008 formula 3 and 0.00454540427936441+0.00452303537205577*[K2O]+0.00026538565533632*[B2O3]+2.211176044138×10 -5 *[Al2O3]*[BaO]+6.27439041968789×10 -6 *2[CaO]-0.000215116681577554*[F]-6.01991751010702×10 -6 *[SiO2]*[B2O3]≦0.008 Equation 4 85. The article of claim 84, wherein the article is defined by at least one of the following:

[0243] An 86th aspect of the present disclosure relates to the article of any one of the 84th or 85th aspects, wherein the glass further has a dielectric constant of about 7.5 or less and a loss tangent of about 0.005 or less, as measured with a 10 GHz signal.

[0244] An 87th aspect of the present disclosure relates to the article of any one of aspects 84 or 85, wherein the glass further has a dielectric constant of about 5 or less and a loss tangent of about 0.005 or less, as measured with a 10 GHz signal.

[0245] An eighty-eighth aspect of the present disclosure is a method for producing a glass comprising the steps of: providing a glass having a first total X, in mole percent of oxides, present in the glass; sum , the sum of the second Y sum , and the sum of the third Z sum is equal to 100.

[0246] An eighty-ninth aspect of the present disclosure relates to the article of any one of aspects 84 to 88, wherein the glass further comprises MgO and ZnO.

[0247] A 90th aspect of the present disclosure relates to the article of any one of aspects 84 to 89, wherein the glass further comprises SnO2 and at least one of CaO and BaO.

[0248] A ninety-first aspect of the present disclosure relates to the article of any one of aspects 84 to 90, wherein the glass comprises no more than trace amounts of alkali metal oxides.

[0249] A ninety-second aspect of the present disclosure relates to the article of any one of aspects 84 to 91, wherein the glass is substantially free of at least one of F, La2O3, and ZnO.

[0250] A 93rd aspect of the present disclosure relates to the article of any one of aspects 84 to 92, wherein the glass further comprises at least one of F, La2O3, and ZnO.

[0251] It should be emphasized that the above-described embodiments of the present disclosure, including any embodiments, are merely possible implementations and are provided merely for a clear understanding of the various principles of the present disclosure. Many changes and modifications may be made to the above-described embodiments of the present disclosure without substantially departing from the spirit and various principles of the present disclosure. All such modifications and modifications are intended to be included herein within the scope of the present disclosure and protected by the following claims.

[0252] Preferred embodiments of the present invention will be described below in detail.

[0253] EMBODIMENT 1 An article, The above items are: Glass: About 60% to about 80% SiO2; 0% to about 13% Al2O3; About 15% to about 28% B2O3; 0% to about 1% of at least one fining agent; and One or more alkaline earth oxides (RO) ranging from 0% to about 15% total (by mole percent of oxide) wherein RO comprises a glass selected from CaO, MgO, BaO, and SrO; The ratio of B2O3:(Al2O3+SiO2) is about 0.13 to about 0.35, The article, wherein the glass has a dielectric constant of about 10 or less and a loss tangent of about 0.01 or less, both measured with a 10 GHz signal.

[0254] EMBODIMENT 2 2. The article of claim 1, wherein the fining agent comprises one or more of SnO2, Sb2O3, As2O3, and a halogen salt.

[0255] EMBODIMENT 3 2. The article of embodiment 1, wherein the glass further comprises (by oxide mole percent) about 2% to about 15% combined of one or more of CaO, MgO, BaO, and SrO.

[0256] EMBODIMENT 4 4. The article of embodiment 3, wherein the glass further comprises (in oxide mole percent) about 1% to about 13% MgO and about 0.1% to about 10% CaO.

[0257] EMBODIMENT 5 2. The article of claim 1, wherein the glass comprises greater than 0 mol % and less than or equal to 8.5 mol % RO and further has a dielectric constant less than or equal to about 6 and / or a loss tangent less than or equal to about 0.004, both measured with a 10 GHz signal.

[0258] EMBODIMENT 6 2. The article of embodiment 1, wherein the ratio of B2O3:(Al2O3+SiO2) is about 0.22 to about 0.35.

[0259] EMBODIMENT 7 2. The article of embodiment 1, wherein the ratio of RO:(Al2O3+(0.5*B2O3)) is from 0 to about 0.9.

[0260] EMBODIMENT 8 2. The article of embodiment 1, wherein the ratio of RO:(Al2O3+(0.5*B2O3)) is from about 0.2 to about 0.9.

[0261] EMBODIMENT 9 The above glasses contain (in mole percent oxides): About 64% to about 75% SiO2; about 1% to about 12% Al2O3; and Approximately 16% to 26% B2O3 2. The article of embodiment 1, further comprising:

[0262] EMBODIMENT 10 10. The article of any one of the preceding claims, wherein the glass has a dielectric constant of about 7.5 or less and a loss tangent of about 0.005 or less, as measured with a 10 GHz signal.

[0263] EMBODIMENT 11 10. The article of any one of the preceding claims, wherein the glass has a dielectric constant of about 5 or less, and a loss tangent of about 0.005 or less, as measured with a 10 GHz signal.

[0264] EMBODIMENT 12 12. The article of any one of the preceding claims, wherein the glass comprises no more than trace amounts of alkali metal oxides.

[0265] EMBODIMENT 13 The above glass has a melting point of approximately 25×10 when measured at 0℃ to 300℃. -7 / ℃ ~ approx. 65×10 -7 13. The article of any one of claims 1-12, having an average coefficient of thermal expansion (CTE) of 1.0 / °C.

[0266] EMBODIMENT 14 14. The article of any one of the preceding claims, wherein the glass has dimensional stability at 260°C for 30 seconds.

[0267] EMBODIMENT 15 An article, The above items are: Glass: About 60% to about 80% SiO2; 0% to about 13% Al2O3; About 15% to about 28% B2O3; 0% to about 1% of at least one fining agent; and One or more alkaline earth oxides (RO) ranging from 0% to about 15% total (by mole percent of oxide) wherein RO comprises a glass selected from CaO, MgO, BaO, and SrO; The ratio of RO:(Al2O3+(0.5*B2O3)) is from about 0 to about 0.9; The glass has a liquidus viscosity of about 40 kpoise to about 5000 kpoise.

[0268] EMBODIMENT 16 16. The article of embodiment 15, wherein the fining agent comprises one or more of SnO2, Sb2O3, As2O3, and a halogen salt.

[0269] EMBODIMENT 17 17. The article of embodiment 16, wherein the glass further comprises (by oxide mole percent) about 2% to about 15% combined of one or more of CaO, MgO, BaO, and SrO.

[0270] EMBODIMENT 18 18. The article of embodiment 17, wherein the glass further comprises (in oxide mole percent) about 1% to about 13% MgO and about 0.1% to about 10% CaO.

[0271] EMBODIMENT 19 16. The article of claim 15, wherein the glass comprises greater than 0 mol % and less than or equal to 8.5 mol % RO and further has a dielectric constant less than or equal to about 6 and / or a loss tangent less than or equal to about 0.004, both measured with a 10 GHz signal.

[0272] EMBODIMENT 20 16. The article of embodiment 15, wherein the ratio of RO:(Al2O3+(0.5*B2O3)) is from about 0.2 to about 0.9.

[0273] EMBODIMENT 21 16. The article of embodiment 15, wherein the ratio of B2O3:(Al2O3+SiO2) is from about 0.13 to about 0.35.

[0274] EMBODIMENT 22 22. The article of embodiment 21, wherein the ratio of B2O3:(Al2O3+SiO2) is from about 0.22 to about 0.35.

[0275] EMBODIMENT 23 The above glasses contain (in mole percent oxides): About 65% to about 80% SiO2; about 1% to about 8% Al2O3; and Approximately 16% to 26% B2O3 16. The article of embodiment 15, further comprising:

[0276] EMBODIMENT 24 24. The article of any one of claims 15-23, wherein the glass further has a 35,000 poise temperature of from about 1110°C to about 1325°C.

[0277] EMBODIMENT 25 25. The article of any one of claims 15-24, wherein the glass further has a 200 poise melting point of from about 1600°C to about 1825°C.

[0278] EMBODIMENT 26 26. The article of any one of claims 15-25, wherein the glass contains no more than trace amounts of alkali metal oxides.

[0279] EMBODIMENT 27 The above glass has a melting point of approximately 25×10 when measured at 0℃ to 300℃. -7 / ℃ ~ approx. 65×10 -7 27. The article of any one of claims 15-26, having an average coefficient of thermal expansion (CTE) of 100 / °C.

[0280] EMBODIMENT 28 28. The article of any one of claims 15-27, wherein the glass further has a liquidus viscosity of about 50 kpoise to about 3000 kpoise.

[0281] EMBODIMENT 29 29. The article of any one of claims 15 to 28, wherein the glass has dimensional stability at 260°C for 30 seconds.

[0282] EMBODIMENT 30 An article, The above items are: Glass: About 60% to about 80% SiO2; 0% to about 13% Al2O3; About 15% to about 28% B2O3; 0% to about 1% of at least one fining agent; and One or more alkaline earth oxides (RO) ranging from 0% to about 15% total (by mole percent of oxide) wherein RO comprises a glass selected from CaO, MgO, BaO, and SrO; The ratio of B2O3:(Al2O3+SiO2) is about 0.13 to about 0.35, the glass has a dielectric constant of about 10 or less and a loss tangent of about 0.01 or less when measured with a 10 GHz signal; The article further comprises the glass having a liquidus viscosity of about 40 kpoise to about 5000 kpoise.

[0283] EMBODIMENT 31 31. The article of embodiment 30, wherein the fining agent comprises one or more of SnO2, Sb2O3, As2O3, and a halogen salt.

[0284] EMBODIMENT 32 31. The article of claim 30, wherein the glass has a dielectric constant of about 7.5 or less and a loss tangent of about 0.005 or less, as measured with a 10 GHz signal.

[0285] EMBODIMENT 33 31. The article of claim 30, wherein the glass has a dielectric constant of about 5 or less and a loss tangent of about 0.005 or less, as measured with a 10 GHz signal.

[0286] EMBODIMENT 34 34. The article of any one of claims 30-33, wherein the glass has a liquidus viscosity of about 50 kpoise to about 3000 kpoise.

[0287] EMBODIMENT 35 35. The article of any one of claims 30-34, wherein the glass further has a 35,000 poise temperature of from about 1110°C to about 1325°C.

[0288] EMBODIMENT 36 The above glasses contain (in mole percent oxides): About 64% to about 75% SiO2; about 1% to about 12% Al2O3; and Approximately 16% to 26% B2O3 36. The article of any one of embodiments 30-35, further comprising:

[0289] EMBODIMENT 37 31. The article of embodiment 30, wherein the ratio of B2O3:(Al2O3+SiO2) is from about 0.22 to about 0.35.

[0290] EMBODIMENT 38 31. The article of embodiment 30, wherein the ratio of RO:(Al2O3+(0.5*B2O3)) is from about 0 to about 0.9.

[0291] EMBODIMENT 39 39. The article of embodiment 38, wherein the ratio of RO:(Al2O3+(0.5*B2O3)) is from about 0.2 to about 0.9.

[0292] EMBODIMENT 40 An article, The above items are: Glass: About 60% to about 80% SiO2; 0% to about 13% Al2O3; About 15% to about 28% B2O3; 0% to about 1% of at least one fining agent; and MgO and at least one additional alkaline earth oxide (RO) wherein the at least one additional RO is selected from CaO, BaO, and SrO, and the total amount of MgO and the at least one additional RO (RO Total) is about 3% to about 15% (by oxide mole percent); The article, wherein the glass has a dielectric constant of about 10 or less and / or a loss tangent of about 0.01 or less, both measured with a 10 GHz signal.

[0293] EMBODIMENT 41 41. The article of embodiment 40, further having a loss tangent of less than or equal to about 0.008 when measured with a 10 GHz signal.

[0294] EMBODIMENT 42 41. The article of claim 40, wherein the glass has a dielectric constant of about 7.5 or less and a loss tangent of about 0.005 or less, both measured with a 10 GHz signal.

[0295] EMBODIMENT 43 MgO:RO Total 43. The article of any one of embodiments 40-42, wherein the ratio is at least 0.3.

[0296] EMBODIMENT 44 MgO:RO Total 43. The article of any one of embodiments 40-42, wherein the ratio is at least 0.5.

[0297] EMBODIMENT 45 RO Total is about 4% to about 15 mol % (in terms of oxide mole percent).

[0298] EMBODIMENT 46 RO Total 46. ​​The article of any one of embodiments 40-45, wherein the ratio of Al2O3 to Al2O3 is greater than 1.

[0299] EMBODIMENT 47 47. The article of any one of embodiments 40-46, wherein the ratio of B2O3:(Al2O3+SiO2) is from about 0.13 to about 0.35.

[0300] EMBODIMENT 48 48. The article of any one of embodiments 40-47, wherein the at least one additional RO is CaO, and further wherein (in terms of oxide mole percent) MgO is present in an amount between about 1% and about 10%, and CaO is present in an amount between about 1% and about 10%.

[0301] EMBODIMENT 49 48. The article of any one of embodiments 40-47, wherein the at least one additional RO is CaO, and further wherein (in terms of oxide mole percent) MgO is present in an amount between about 1% and about 7%, and CaO is present in an amount between about 2% and about 7%.

[0302] EMBODIMENT 50 48. The article of any one of embodiments 40-47, wherein the at least one additional RO is SrO, and further wherein (in terms of oxide mole percent) MgO is present in an amount between about 1% and about 10% and SrO is present in an amount between about 1% and about 5%.

[0303] EMBODIMENT 51 51. The article of any one of embodiments 40-50, wherein the fining agent comprises one or more of SnO2, Sb2O3, As2O3, and a halogen salt.

[0304] EMBODIMENT 52 RO Total 52. The article of any one of embodiments 40-51, wherein the ratio of (Al2O3+B2O3) is from about 0.2 to about 0.6.

[0305] EMBODIMENT 53 53. The article of any one of embodiments 40-52, wherein the glass is substantially free of alkali metal oxides.

[0306] EMBODIMENT 54 54. The article of any one of claims 40 to 53, wherein the glass has a density of about 2.2 to about 2.5 grams per cubic centimeter when measured at about 25° C.

[0307] EMBODIMENT 55 55. The article of any one of claims 40-54, wherein the glass further has a 35,000 poise temperature of from about 1110°C to about 1325°C.

[0308] EMBODIMENT 56 56. The article of any one of claims 40-55, wherein the glass further has a 200 poise melting point of from about 1600°C to about 1825°C.

[0309] EMBODIMENT 57 An article for a substrate of an electronic device, comprising: The above items are: Glass: About 60% to about 80% SiO2; 0% to about 13% Al2O3; About 15% to about 28% B2O3; 0% to about 1% of at least one fining agent; and MgO and at least one additional alkaline earth oxide (RO) wherein the at least one additional RO is selected from CaO, BaO, and SrO, and the total amount of MgO and the at least one additional RO (RO Total ) is about 3% to about 15% (by oxide mole percent); The article, wherein the glass has a dielectric constant of about 10 or less and / or a loss tangent of about 0.01 or less, both measured with a 10 GHz signal.

[0310] EMBODIMENT 58 58. The article of embodiment 57, further having a loss tangent of less than or equal to about 0.008 when measured with a 10 GHz signal.

[0311] EMBODIMENT 59 58. The article of claim 57, wherein the glass has a dielectric constant of about 7.5 or less and a loss tangent of about 0.005 or less, both measured with a 10 GHz signal.

[0312] EMBODIMENT 60 MgO:RO Total60. The article of any one of embodiments 57-59, wherein the ratio is at least 0.3.

[0313] EMBODIMENT 61 MgO:RO Total 60. The article of any one of embodiments 57-59, wherein the ratio is at least 0.5.

[0314] EMBODIMENT 62 RO Total is about 4% to about 15 mol % (in terms of oxide mole percent).

[0315] EMBODIMENT 63 RO Total 63. The article of any one of embodiments 57-62, wherein the ratio of Al2O3 to Al2O3 is greater than 1.

[0316] EMBODIMENT 64 64. The article of any one of embodiments 57-63, wherein the ratio of B2O3:(Al2O3+SiO2) is from about 0.13 to about 0.35.

[0317] EMBODIMENT 65 65. The article of any one of embodiments 57-64, wherein the at least one additional RO is CaO, and further wherein (in terms of oxide mole percent) MgO is present in an amount between about 1% and about 10%, and CaO is present in an amount between about 1% and about 10%.

[0318] EMBODIMENT 66 65. The article of any one of embodiments 57-64, wherein the at least one additional RO is CaO, and further wherein (in terms of oxide mole percent) MgO is present in an amount between about 1% and about 7%, and CaO is present in an amount between about 2% and about 7%.

[0319] EMBODIMENT 67 65. The article of any one of embodiments 57-64, wherein the at least one additional RO is SrO, and further wherein (in terms of oxide mole percent) MgO is present in an amount between about 1% and about 10% and SrO is present in an amount between about 1% and about 5%.

[0320] EMBODIMENT 68 68. The article of any one of embodiments 57-67, wherein the fining agent comprises one or more of SnO2, Sb2O3, As2O3, and a halogen salt.

[0321] EMBODIMENT 69 RO Total 69. The article of any one of embodiments 57-68, wherein the ratio of (Al2O3+B2O3) is from about 0.2 to about 0.6.

[0322] EMBODIMENT 70 70. The article of any one of embodiments 57-69, wherein the glass is substantially free of alkali metal oxides.

[0323] EMBODIMENT 71 71. The article of any one of claims 57 to 70, wherein the glass has a density of about 2.2 to about 2.5 grams per cubic centimeter when measured at about 25° C.

[0324] EMBODIMENT 72 72. The article of any one of claims 57-71, wherein the glass further has a 35,000 poise temperature of from about 1110°C to about 1325°C.

[0325] EMBODIMENT 73 73. The article of any one of claims 57-72, wherein the glass further has a 200 poise melting point of about 1600°C to about 1825°C.

[0326] EMBODIMENT 74 An article, The above items are: Glass: SiO2, Al2O3, and B2O3; and At least one of Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, SnO2, ZnO, La2O3, F, and Fe2O3 The glass includes The first sum of SiO2, Al2O3, and B2O3 (X sum), the second sum of Li2O, Na2O, K2O, MgO, CaO, SrO, and BaO (Y sum ), and the sum of SnO2, ZnO, La2O3, F, and Fe2O3 third (Z sum )(X sum , Y sum , and Z sum is the mole percent of oxide) at the boundary points: TIFF2025039835000025.tif45155

[0327] X as further defined by sum , Y sum , and Z sum is in the convex hull of The glass further comprises a compound represented by Formula 1 and Formula 2 (in mole percent of oxides): -42.8440902+0.463763055*[SiO2]+0.520077325*[Al2O3]+0.468168738 *[B2O3]+0.47253232*[Li2O]+2.11958583*[K2O]+0.499421381*[MgO]+0. 558094225*[CaO]+0.805792958*[SrO]+0.637349469*[BaO]-0.17232118* [SnO2]+0.525853343*[ZnO]+0.261394654*[La2O3]+0.469279089*[F]≦10 formula 1 and 0.756212572817506+[K2O]+0.209148876828416*[La2O3]+0.0884393206156657*[BaO]+0.0384462744417 211*[CaO]+(5.95212630529679-[F]) / [B2O3]+(254.196472343803-2.1615185467817*[B2O3]) / [SiO2]≦10 formula 2 is defined by at least one of Further, the glass has a dielectric constant of about 10 or less when measured with a 10 GHz signal.

[0328] EMBODIMENT 75 The glass further has a loss tangent of about 0.008 or less as measured with a 10 GHz signal, and the glass further has a glass composition satisfying Formula 3 and Formula 4 (in mole percent of oxides): 0.429780863-0.00424207*[SiO2]-0.004096119*[Al2O3]-0.004396116*[B 2O3]-0.002791817*[Li2O]-0.012890989*[K2O]-0.004226519*[MgO]-0.00 4108234*[CaO]-0.003587217*[SrO]-0.004083111*[BaO]-0.028056812*[S nO2]-0.004220402*[ZnO]+0.000195707*[La2O3]-0.004466313*[F]≦0.008 formula 3 and 0.00454540427936441+0.00452303537205577*[K2O]+0.00026538565533632*[B2O3]+2.211176044138×10 -5 *[Al2O3]*[BaO]+6.27439041968789×10 -6 *2[CaO]-0.000215116681577554*[F]-6.01991751010702×10 -6 *[SiO2]*[B2O3]≦0.008 Equation 4 75. The article of embodiment 74, defined by at least one of:

[0329] EMBODIMENT 76 76. The article of claim 74 or 75, wherein the glass further has a dielectric constant of about 7.5 or less and a loss tangent of about 0.005 or less, as measured with a 10 GHz signal.

[0330] EMBODIMENT 77 76. The article of claim 74 or 75, wherein the glass further has a dielectric constant of about 5 or less and a loss tangent of about 0.005 or less, as measured with a 10 GHz signal.

[0331] EMBODIMENT 78 The first total X present in the glass in mole percent of oxides sum , the sum of the second Y sum , and the sum of the third Z sum The article of any one of embodiments 74-77, wherein is equal to 100.

[0332] EMBODIMENT 79 79. The article of any one of claims 74-78, wherein the glass further comprises MgO and ZnO.

[0333] EMBODIMENT 80 80. The article of any one of claims 74-79, wherein the glass further comprises SnO2 and at least one of CaO and BaO.

[0334] Embodiment 81 81. The article of any one of claims 74-80, wherein the glass contains no more than trace amounts of alkali metal oxides.

[0335] EMBODIMENT 82 82. The article of any one of embodiments 74-81, wherein the glass is substantially free of at least one of F, La2O3, and ZnO.

[0336] EMBODIMENT 83 82. The article of any one of claims 74-81, wherein the glass further comprises at least one of F, La2O3, and ZnO.

[0337] EMBODIMENT 84 An article, The above items are: Glass: SiO2, Al2O3, and B2O3; and At least one of Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, SnO2, ZnO, La2O3, F, and Fe2O3 The glass includes The first sum of SiO2, Al2O3, and B2O3 (X sum), the second sum of Li2O, Na2O, K2O, MgO, CaO, SrO, and BaO (Y sum ), and the sum of SnO2, ZnO, La2O3, F, and Fe2O3 third (Z sum )(X sum , Y sum , and Z sum is the mole percent of oxide) at the boundary points: TIFF2025039835000026.tif97157

[0338] X as further defined by sum , Y sum , and Z sum is in the convex hull of The glass further comprises a compound represented by Formula 1 and Formula 2 (in mole percent of oxides): -42.8440902+0.463763055*[SiO2]+0.520077325*[Al2O3]+0.468168738 *[B2O3]+0.47253232*[Li2O]+2.11958583*[K2O]+0.499421381*[MgO]+0. 558094225*[CaO]+0.805792958*[SrO]+0.637349469*[BaO]-0.17232118* [SnO2]+0.525853343*[ZnO]+0.261394654*[La2O3]+0.469279089*[F]≦10 formula 1 and 0.756212572817506+[K2O]+0.209148876828416*[La2O3]+0.0884393206156657*[BaO]+0.0384462744417 211*[CaO]+(5.95212630529679-[F]) / [B2O3]+(254.196472343803-2.1615185467817*[B2O3]) / [SiO2]≦10 formula 2 is defined by at least one of The glass further has a dielectric constant of about 10 or less when measured with a 10 GHz signal.

[0339] EMBODIMENT 85 The glass further has a loss tangent of about 0.008 or less as measured with a 10 GHz signal, and the glass further has a glass composition satisfying Formula 3 and Formula 4 (in mole percent of oxides): 0.429780863-0.00424207*[SiO2]-0.004096119*[Al2O3]-0.004396116*[B 2O3]-0.002791817*[Li2O]-0.012890989*[K2O]-0.004226519*[MgO]-0.00 4108234*[CaO]-0.003587217*[SrO]-0.004083111*[BaO]-0.028056812*[S nO2]-0.004220402*[ZnO]+0.000195707*[La2O3]-0.004466313*[F]≦0.008 formula 3 and 0.00454540427936441+0.00452303537205577*[K2O]+0.00026538565533632*[B2O3]+2.211176044138×10 -5 *[Al2O3]*[BaO]+6.27439041968789×10 -6 *2[CaO]-0.000215116681577554*[F]-6.01991751010702×10 -6 *[SiO2]*[B2O3]≦0.008 Equation 4 85. The article of embodiment 84, defined by at least one of:

[0340] EMBODIMENT 86 86. The article of claim 84 or 85, wherein the glass further has a dielectric constant of about 7.5 or less and a loss tangent of about 0.005 or less, as measured with a 10 GHz signal.

[0341] EMBODIMENT 87 86. The article of claim 84 or 85, wherein the glass further has a dielectric constant of about 5 or less and a loss tangent of about 0.005 or less, as measured with a 10 GHz signal.

[0342] EMBODIMENT 88 The first total X present in the glass in mole percent of oxides sum , the sum of the second Y sum , and the sum of the third Z sum The article of any one of embodiments 84-87, wherein is equal to 100.

[0343] EMBODIMENT 89 89. The article of any one of embodiments 84-88, wherein the glass further comprises MgO and ZnO.

[0344] EMBODIMENT 90 90. The article of any one of claims 84-89, wherein the glass further comprises SnO2 and at least one of CaO and BaO.

[0345] EMBODIMENT 91 91. The article of any one of claims 84-90, wherein the glass contains no more than trace amounts of alkali metal oxides.

[0346] EMBODIMENT 92 92. The article of any one of embodiments 84-91, wherein the glass is substantially free of at least one of F, La2O3, and ZnO.

[0347] EMBODIMENT 93 93. The article of any one of claims 84-92, wherein the glass further comprises at least one of F, La2O3, and ZnO.

[0348] EMBODIMENT 94 An article, The article comprises: Glass: About 60% to about 80% SiO2; 0% to about 13% Al2O3; About 15% to about 28% B2O3; 0% to about 1% of at least one fining agent; and MgO and at least one additional alkaline earth oxide (RO) wherein the at least one additional RO is selected from CaO, BaO, and SrO, and the total amount of MgO and the at least one additional RO (RO Total ) is about 3% to about 15% (by oxide mole percent); The article, wherein the glass has a dielectric constant of about 10 or less and / or a loss tangent of about 0.01 or less, both measured with a 10 GHz signal.

[0349] EMBODIMENT 95 95. The article of embodiment 94, further having a loss tangent of less than or equal to about 0.008 when measured with a 10 GHz signal.

[0350] EMBODIMENT 96 95. The article of claim 94, wherein the glass has a dielectric constant of about 7.5 or less and a loss tangent of about 0.005 or less, both measured with a 10 GHz signal.

[0351] EMBODIMENT 97 MgO:RO Total 97. The article of any one of embodiments 94-96, wherein the ratio is at least 0.5.

[0352] EMBODIMENT 98 RO Total The article of any one of embodiments 94-97, wherein (in terms of oxide mole percent) is about 4% to about 15 mol %.

[0353] EMBODIMENT 99 RO Total 99. The article of any one of embodiments 94-98, wherein the ratio of Al2O3 to Al2O3 is greater than 1.

[0354] EMBODIMENT 100 100. The article of any one of embodiments 94-99, wherein the ratio of B2O3:(Al2O3+SiO2) is from about 0.13 to about 0.35.

[0355] EMBODIMENT 101 101. The article of any one of embodiments 94-100, wherein the at least one additional RO is CaO, and further wherein (in mole percent of oxides) MgO is present in an amount between about 1% and about 7% and CaO is present in an amount between about 2% and about 7%.

[0356] EMBODIMENT 102 RO Total 102. The article of any one of embodiments 94-101, wherein the ratio of (Al2O3+SiO2) is from about 0.2 to about 0.6.

Claims

1. An article, The article comprises: A glass having, in mole percent oxide, 60% to 80% SiO 2 , 0% to 13% Al 2 O 3 , 15% to 20% B 2 O 3 , 0% to 1% of at least one fining agent, and MgO and at least one additional alkaline earth oxide (RO) selected from CaO, BaO, and SrO Including, The total amount of MgO and the at least one additional RO (RO Total ) is between 3% and 15% by mole percent of oxide, with a ratio of MgO:RO between 0.38 and 0.86; The article, wherein the glass has a dielectric constant of 10 or less and / or a loss tangent of 0.01 or less when measured with a 10 GHz signal.

2. 10. The article of claim 1, further having a loss tangent of less than or equal to 0.008 when measured with a 10 GHz signal.

3. 10. The article of claim 1, wherein the glass has a dielectric constant of 7.5 or less, and a loss tangent of 0.005 or less, both measured with a 10 GHz signal.

4. MgO:RO Total The article of claim 1 , wherein the ratio is at least 0.

5.

5. RO Total The article of any one of claims 1 to 3, wherein, in terms of mole percent of oxide, is between 4% and 15 mole%.

6. RO Total :Al 2 O 3 The article of any one of claims 1 to 3, wherein the ratio of

7. B 2 O 3 :(Al 2 O 3 +SiO 2 4. The article according to claim 1, wherein the ratio of 0.13 to 0.

35.

8. The article of any one of claims 1 to 3, wherein the at least one additional RO is CaO, and further wherein, in mole percent of oxides, MgO is present in an amount between 1% and 7% and CaO is present in an amount between 2% and 7%.

9. RO Total :(Al 2 O 3 +B 2 O 3 4. The article according to claim 1, wherein the ratio of

Citation Information

Patent Citations

  • glass

    JP2016102045A

  • Low dielectric constant low temperature fired ceramics

    US20040198580A1

  • Low dielectric glass composition, fibers, and article

    WO2018125736A1

  • Glass composition for glass fiber, glass fiber, and glass fiber-reinforced resin composition using same

    WO2019049526A1